Heat transfer suppression member and battery pack

JP2025021443APending Publication Date: 2025-02-13IBIDEN CO LTD

Patent Information

Application Number
JP2024115979
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-31
Filing Date
2024-07-19
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0031】 本発明の熱伝達抑制シートは、無機粒子と、有機繊維又は無機繊維と、を含む断熱材を有するため、優れた断熱性を得ることができる。また、断熱材に弾性シートが積層されているため、弾性シートが電池セルの変形を吸収し、電池ケースの破壊及び電池の性能の低下を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021443000001_ABST
    Figure 2025021443000001_ABST
Patent Text Reader

Abstract

To provide a heat transfer suppression sheet that can further suppress the propagation of heat between battery cells in the event of an abnormality and suppress the destruction of the battery case and the deterioration of battery performance due to deformation of the battery cells, and to provide a battery pack that can suppress the destruction of the battery case and the deterioration of battery performance while suppressing the propagation of heat between the battery cells, and that is easy to design and assemble.SOLUTION: A heat transfer suppression sheet 50 has: an insulating material 10 having inorganic particles 4 and organic fibres 1 or inorganic fibres 15; and an elastic sheet 51 laminated on at least one of a first surface 10a and a second surface 10b that are perpendicular to the thickness direction of the insulating material 10. In addition, a battery pack 100 has a plurality of battery cells 20a, 20b, 20c and the heat transfer suppression sheet 50. The plurality of battery cells 20a, 20b, 20c are connected in series or in parallel.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat transfer-suppressing sheet and a battery pack having the heat transfer-suppressing sheet. [Background technology]

[0002] In recent years, from the viewpoint of environmental protection, active development of electric vehicles, hybrid vehicles, etc. that are driven by electric motors is underway. These electric vehicles, hybrid vehicles, etc. are equipped with assembled batteries in which multiple battery cells are connected in series or parallel to serve as the power source for the driving electric motor.

[0003] Furthermore, these battery cells mainly use lithium-ion secondary batteries, which are capable of higher capacity and higher output than lead-acid batteries, nickel-metal hydride batteries, etc. If a certain battery cell experiences thermal runaway, in which the temperature rises suddenly and the cell continues to generate heat due to an internal short circuit or overcharging, the heat from the battery cell experiencing thermal runaway may propagate to other adjacent battery cells, causing thermal runaway in the other battery cells.

[0004] As a countermeasure against the occurrence of thermal runaway as described above, for example, Patent Document 1 proposes an assembled battery that can prevent or suppress the spread of fire to adjacent battery cells when abnormal heat occurs due to an overcurrent flowing into a battery cell. The assembled battery described in Patent Document 1 is composed of multiple battery cells and a block made of a metal material that holds the cells, and this block is composed of multiple small blocks. In addition, the size of the gap between the block and the battery cells is adjusted.

[0005] In the battery pack described in Patent Document 1 configured as above, the blocks that hold the battery cells are made of a metallic material, which is said to enable quick diffusion of heat.

[0006] Patent Document 2 discloses a battery pack that aims to improve the heat dissipation of secondary batteries and prevent performance degradation. The battery pack described in Patent Document 2 has multiple secondary batteries housed in a case, and a plate-shaped rubber sheet that has a thermal conductivity equal to or greater than a predetermined value and changes shape when subjected to pressure is disposed between the multiple secondary batteries and the case.

[0007] According to the above-mentioned Patent Document 2, since the thermal conductivity of the rubber sheet is relatively high, the heat of the secondary battery can be effectively discharged through the case. In addition, since the rubber sheet of this battery pack has elasticity, it is possible to prevent damage when the battery pack is dropped. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2014-96271 A [Patent Document 2] JP 2004-146161 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, when thermal runaway occurs in a battery cell, gas is generated inside the battery, causing the internal pressure to rise and deforming the battery cell. If this deformation is severe, the case may be destroyed. This type of battery cell deformation occurs slightly even when battery cells assembled into a battery are subjected to a charge / discharge cycle (i.e., during "normal use"). When the internal pressure of the battery cell repeatedly rises and falls during charging and discharging, the battery cell is repeatedly pressed and released by the case, causing a decrease in battery performance.

[0010] The battery pack described in Patent Document 1 above has blocks that hold the battery cells and are made of metal material, which allows heat to be diffused quickly. However, no consideration is given to the risk of damage to the battery case or deterioration of battery performance due to deformation of the battery cells. In addition, the battery pack described in Patent Document 1 requires multiple blocks, and the gap between the blocks and the battery cells is changed, so the blocks need to be designed according to the electronic device, power tool, etc. in which the battery pack is to be installed. This poses the problem that the design of the blocks and the assembly of the battery pack are complicated.

[0011] Furthermore, the battery pack described in Patent Document 2 does not take into consideration the prevention of thermal runaway in other adjacent battery cells when thermal runaway occurs in one battery cell.

[0012] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a heat transfer suppression sheet that can further suppress the propagation of heat between battery cells in the event of an abnormality and suppress damage to the battery case and deterioration of battery performance due to deformation of the battery cells, and a battery pack that is easy to design and assemble and can suppress the propagation of heat between battery cells while suppressing damage to the battery case and deterioration of battery performance. [Means for solving the problem]

[0013] The above object of the present invention can be achieved by the heat-transfer-suppressing sheet having the following configuration [1].

[0014] [1] An insulating material having inorganic particles and organic or inorganic fibers; a heat-transfer-suppressing sheet comprising: an elastic sheet laminated on at least one of a first surface and a second surface of the heat insulating material that are perpendicular to the thickness direction of the heat insulating material;

[0015] Further, preferred embodiments of the present invention relating to the heat-transfer-suppressing sheet relate to the following items [2] to

[14] .

[0016] [2] The heat-transfer-suppressing sheet described in [1], characterized in that the heat insulating material has a plurality of three-dimensionally connected pores.

[0017] [3] The heat transfer-suppressing sheet according to [1] or [2], characterized in that when the insulating material contains organic fibers, the organic fibers have a welded portion covering at least a portion of a surface thereof, and at least a portion of the inorganic particles are welded to the organic fibers by the welded portion.

[0018] [4] In the thermal insulation material, the organic fiber is made of a first organic material, and the welded portion contains a second organic material; The heat-transfer-suppressing sheet according to [3], wherein the melting point of the second organic material is lower than the melting point of the first organic material.

[0019] [5] The heat transfer-suppressing sheet according to [4], wherein in the heat insulating material, the melting point of the second organic material is at least 60° C. lower than the melting point of the first organic material.

[0020] [6] In the thermal insulation material, the first organic material is at least one selected from polyethylene terephthalate, polypropylene, and nylon, The heat transfer-suppressing sheet according to [4] or [5], wherein the second organic material is at least one selected from the group consisting of polyethylene terephthalate, polyethylene, polypropylene, and nylon.

[0021] [7] The heat-transfer-suppressing sheet according to any one of [1] to [6], wherein the heat-insulating material essentially contains the inorganic fibers.

[0022] [8] The heat transfer-suppressing sheet according to [7], wherein the inorganic fibers are at least one type selected from the group consisting of silica-alumina fibers, alumina fibers, silica fibers, rock wool, alkaline earth silicate fibers, and glass fibers.

[0023] [9] The heat-transfer-suppressing sheet according to any one of [3] to [6], characterized in that the heat insulating material has a fiber layer on at least a portion of the first surface and the second surface, in which at least some of the organic fibers are welded to each other by the welded portion.

[0024]

[10] The insulation material further comprises inorganic fibers, The heat transfer-suppressing sheet according to [9], wherein the fiber layer contains the inorganic fibers.

[0025]

[11] The heat-transfer-suppressing sheet according to any one of [1] to

[10] , wherein in the heat-insulating material, the inorganic particles are particles made of at least one type of inorganic material selected from oxide particles, carbide particles, nitride particles, and inorganic hydrate particles.

[0026]

[12] The heat-transfer-suppressing sheet according to any one of [1] to

[11] , wherein in the heat-insulating material, the inorganic particles include at least one type of particles selected from dry silica particles and silica aerogel.

[0027]

[13] The heat transfer-suppressing sheet according to

[12] , characterized in that in the insulating material, the inorganic particles further include at least one type of particles selected from titania, zircon, zirconia, silicon carbide, zinc oxide and alumina.

[0028]

[14] Further, a resin film encapsulating a laminate having the thermal insulation material and the elastic sheet, the resin film has a plurality of holes, and is composed of a first surface side film and a second surface side film arranged on the first surface side and the second surface side of the laminate perpendicular to the thickness direction of the laminate, and an end surface side film arranged on an end surface side parallel to the thickness direction of the laminate, The heat transfer-suppressing sheet according to any one of [1] to

[13] , characterized in that the area ratio of the holes in the first surface side film and the second surface side film to the total area of ​​the first surface side film and the second surface side film is greater than the area ratio of the holes in the end surface side film to the total area of ​​the end surface side film.

[0029] The above object of the present invention can be achieved by the following configuration

[15] relating to a battery pack.

[0030]

[15] An assembled battery comprising a plurality of battery cells and the heat-transfer-suppressing sheet according to any one of [1] to

[14] , the plurality of battery cells being connected in series or in parallel. Effect of the Invention

[0031] The heat-transfer-suppressing sheet of the present invention has an insulating material containing inorganic particles and organic or inorganic fibers, and therefore can provide excellent insulating properties. In addition, since the insulating material is laminated with an elastic sheet, the elastic sheet absorbs deformation of the battery cell, and can suppress breakage of the battery case and deterioration of the battery performance.

[0032] As described above, the battery pack of the present invention has a simple structure, has high thermal insulation properties, and includes a heat transfer suppression sheet that can suppress destruction of the battery case and deterioration of battery performance. Therefore, it is possible to obtain a battery pack that is easy to design and assemble, and can suppress thermal runaway of the battery cells in the battery pack and the spread of flames to the outside of the battery case. [Brief description of the drawings]

[0033] [Figure 1A] FIG. 1A is a schematic cross-sectional view showing a heat-transfer-suppressing sheet according to a first embodiment of the present invention. [Figure 1B] FIG. 1B is a schematic cross-sectional view showing another example of the heat-transfer-suppressing sheet according to the first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a battery pack having a heat transfer-suppressing sheet according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a photograph, substituted for a drawing, showing a first example of the structure of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. [Figure 4] FIG. 4 is a photograph showing an enlarged portion of the heat insulating material shown in FIG. [Diagram 5] FIG. 5 is a photograph, substituted for a drawing, showing a second example of the structure of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. [Figure 6] FIG. 6 is a schematic diagram showing a third example structure of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. [Figure 7] FIG. 7 is a schematic diagram showing an enlarged portion of FIG. [Figure 8] FIG. 8 is a photograph showing the heat insulating material shown in FIG. [Figure 9] FIG. 9 is a photograph, substituted for a drawing, showing a fourth example structure of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. [Figure 10] FIG. 10 is a photograph showing an enlarged view of the structure of the heat insulating material shown in FIG. [Figure 11] FIG. 11 is a photograph showing a cross section of the heat insulating material shown in FIG. [Figure 12] FIG. 12 is a schematic diagram showing a fifth example structure of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. [Figure 13] FIG. 13 is an enlarged schematic view of part A of the heat insulating material shown in FIG. [Figure 14] FIG. 14 is a photograph, substituted for a drawing, showing a sixth example structure of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. [Figure 15] FIG. 15 is a photograph showing another area of ​​the heat insulating material shown in FIG. [Figure 16] FIG. 16 is a photograph showing a cross section of the heat insulating material shown in FIGS. [Figure 17] FIG. 17 is a photograph substituting a drawing that shows a seventh example of a structure of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. [Figure 18]FIG. 18 is a photograph showing an enlarged view of a part of the heat insulating material shown in FIG. [Figure 19] FIG. 19 is a schematic diagram showing an example of a method for defining the length of a fiber bundle. [Figure 20] FIG. 20 is a photograph showing another example of the structure of the heat insulating material shown in FIG. [Figure 21] FIG. 21 is a perspective view showing a heat-transfer suppressing sheet according to a second embodiment of the present invention. [Figure 22] FIG. 22 is a cross-sectional view showing a heat-transfer suppressing sheet according to a second embodiment of the present invention. [Figure 23A] FIG. 23A is a top view showing a heat-transfer suppressing sheet according to a third embodiment of the present invention. [Figure 23B] FIG. 23B is a cross-sectional view taken along line II of the heat-transfer-suppressing sheet according to the third embodiment of the present invention. [Figure 24A] FIG. 24A is a top view showing a heat-transfer suppressing sheet according to a fourth embodiment of the present invention. FIG. [Figure 24B] FIG. 24B is a cross-sectional view taken along line II-II of the heat-transfer-suppressing sheet according to the fourth embodiment of the present invention. [Figure 25A] FIG. 25A is a top view showing a heat-transfer suppressing sheet according to a fifth embodiment of the present invention. FIG. [Figure 25B] FIG. 25B is a cross-sectional view in the thickness direction of the heat-transfer suppressing sheet according to the fifth embodiment of the present invention. [Figure 26A] FIG. 26A is a cross-sectional view in the thickness direction showing a heat-transfer-suppressing sheet according to a sixth embodiment of the present invention. [Figure 26B] FIG. 26B is a top view of the heat transfer suppressing sheet according to the sixth embodiment of the present invention, as viewed from the main surface side. [Figure 27] FIG. 27 is a perspective view showing a heat-transfer suppressing sheet according to a seventh embodiment of the present invention. [Figure 28] FIG. 28 is a perspective view of a modified example of the heat-transfer-suppressing sheet according to the seventh embodiment of the present invention, showing the sheet at a temperature of less than 90° C. [Figure 29]FIG. 29 is a cross-sectional view of a modified example of the heat-transfer-suppressing sheet according to the seventh embodiment of the present invention, showing the state at 90° C. or higher. [Diagram 30] FIG. 30 is a schematic cross-sectional view showing a heat-transfer suppressing sheet according to an eighth embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] The present inventors conducted extensive research to solve the above problems, and discovered that by forming a heat-transfer-suppressing sheet including a thermal insulation material containing inorganic particles and organic or inorganic fibers, and an elastic sheet laminated on the thermal insulation material, it is possible to suppress the application of unnecessary pressure to a battery cell and suppress deterioration of battery performance.

[0035] A heat transfer-suppressing sheet according to an embodiment of the present invention, a manufacturing method thereof, and a battery pack will be described in detail below. Note that the present invention is not limited to the embodiment described below, and can be modified as desired without departing from the gist of the present invention. First, a heat transfer-suppressing sheet according to an embodiment of the present invention will be described.

[0036] [Heat transfer suppression sheet] [First embodiment] Fig. 1A is a schematic cross-sectional view showing a heat-transfer-suppressing sheet according to a first embodiment of the present invention. As shown in Fig. 1A, a heat-transfer-suppressing sheet 50 according to the first embodiment has a thermal insulating material 10 and an elastic sheet 51 laminated on a first surface 10a of the thermal insulating material 10 that is perpendicular to the thickness direction. The thermal insulating material 10 has inorganic particles and organic or inorganic fibers (not shown). The thermal insulating material 10 will be described in detail later. The elastic sheet 51 is obtained by processing an elastic material described later into a sheet shape.

[0037] Fig. 1B is a schematic cross-sectional view showing another example of the heat-transfer-suppressing sheet according to the first embodiment of the present invention. The heat-transfer-suppressing sheet 50 shown in Fig. 1B has a heat-insulating material 10 and an elastic sheet 51 laminated on a first surface 10a and a second surface 10b perpendicular to the thickness direction of the heat-insulating material 10. That is, in the heat-transfer-suppressing sheet 50 shown in Fig. 1B, the heat-insulating material 10 is sandwiched between a pair of elastic sheets 51. The heat-insulating material 10 and the elastic sheet 51 are the same as those of the heat-transfer-suppressing sheet 50 shown in Fig. 1A.

[0038] A specific use form will be described below using the heat-transfer-suppressing sheet 50 shown in Fig. 1B as an example. As shown in Fig. 2, the heat-transfer-suppressing sheet 50 can be used by interposing the heat-transfer-suppressing sheet 50 between a plurality of battery cells 20a, 20b, 20c. The plurality of battery cells 20a, 20b, 20c are connected in series or in parallel (the connected state is not shown) and stored in a battery case 30 to form a battery pack 100. Note that, for example, lithium ion secondary batteries are preferably used as the battery cells 20a, 20b, 20c, but the present invention is not limited thereto and can be applied to other secondary batteries as well.

[0039] The heat transfer-suppressing sheet 50 according to the first embodiment configured as described above has the insulating material 10 having inorganic particles and organic or inorganic fibers, and therefore has excellent thermal insulation properties. Therefore, for example, when an abnormality occurs in the battery cell 20a and the temperature rises, the heat transfer to the battery cell 20b can be sufficiently suppressed. In addition, in the embodiment shown in FIG. 1B, an elastic sheet 51 is laminated on the first surface 10a and the second surface 10b of the insulating material 10. The elastic sheet 51 has an effect of suppressing the deformation of the battery cells 20a, 20b, and 20c, and an effect of absorbing the deformation of the battery cells 20a, 20b, and 20c. That is, when the battery cells 20a, 20b, and 20c deform during charging / discharging or an abnormality, the elastic sheet 51 flexibly deforms in response to the deformation of the battery cells 20a, 20b, and 20c while suppressing the deformation of the battery cells 20a, 20b, and 20c. Therefore, it is possible to suppress the application of unnecessary pressure to the battery cells 20a, 20b, and 20c.

[0040] 1A, even if the elastic sheet 51 is laminated on only one of the first and second surfaces of the thermal insulation material, the presence of the elastic sheet 51 can suppress deformation of the battery cells 20a, 20b, 20c and can provide the effect of absorbing the deformation. The elastic sheet 51 may also be disposed between a pair of thermal insulation materials 10. In either configuration, the properties of the elastic sheet 51 can be utilized, and damage to the battery case and deterioration of the battery performance can be suppressed.

[0041] In the first embodiment, the insulating material 10 may comprise inorganic particles and organic fibers or inorganic fibers (i.e., at least one of organic fibers and inorganic fibers), but an example of an insulating material 10 having even better insulating properties is described in detail below.

[0042] <Thermal insulation material (Structure example 1)> FIG. 3 is a photograph substituting a drawing showing a structural example 1 of an insulating material used in a heat transfer-suppressing sheet according to an embodiment of the present invention, and FIG. 4 is a photograph substituting a drawing showing an enlarged portion of the insulating material shown in FIG. 3.

[0043] As shown in Figures 3 and 4, the insulating material 10 according to the insulating material (Structural Example 1) has inorganic particles 4 and organic fibers 1. The insulating material 10 has a plurality of three-dimensionally connected pores 7 between the inorganic particles 4 and the organic fibers 1. The organic fibers 1 have welded parts 5 covering at least a part of their surface, and at least a part of the inorganic particles 4 are welded to the surface of the organic fibers 1 by the welded parts 5. As a result, the surface of the organic fibers 1 is configured to be covered with the inorganic particles 4.

[0044] The heat insulating material 10 thus configured has a plurality of three-dimensionally connected pores 7, and therefore has the effect of air insulation, thereby improving the heat insulating performance. Furthermore, the heat insulating material 10 contains organic fibers 1 that have high flexibility, and therefore the flexibility of the heat insulating material 10 can be increased, and the organic fibers 1 can be easily entangled with each other, thereby improving the sheet strength. Therefore, the destruction of the heat transfer suppressing sheet having such heat insulating material 10 can be suppressed. Furthermore, the presence of the pores 7 in the heat insulating material 10 improves the cushioning properties of the entire sheet, so that when the battery cells 20a, 20b, and 20c expand during charging and discharging, the heat insulating material 10, together with the elastic sheet 51, absorbs the expansion of the battery cells, and the deterioration of the performance of the battery cells can be further suppressed.

[0045] Furthermore, in this embodiment, it is preferable that at least some of the pores 7 communicate with the surface of the insulating material 10 and open outward. With the pores 7 configured in this manner, even if the insulating material 10 becomes hot and the organic fibers 1 and the like are decomposed when the adjacent battery cells 20a, 20b, 20c experience thermal runaway, the decomposition gas is not retained inside the sheet but is released to the outside via the pores 7. Therefore, from this point of view as well, the effect of preventing destruction of the sheet can be obtained.

[0046] Furthermore, when the welded portions 5 on the outer peripheral surface of the organic fibers 1 fix the inorganic particles 4 to the organic fibers 1, it is possible to obtain the effect of suppressing the falling off (powdering) of the inorganic particles 4. Therefore, even if, for example, part of the battery cells 20a, 20b, 20c expands and compressive stress or impact is applied to the heat-transfer-suppressing sheet 50, the effect of maintaining the shape of the insulating material 10 can be further enhanced, and a decrease in the insulating effect due to compressive deformation of the insulating material 10 can be prevented.

[0047] In this specification, the welded parts 5 refer to the parts where the surfaces of the organic fibers 1 melt and then solidify again, and are formed in the manufacturing process of the thermal insulation material 10 described below. In this embodiment, the inorganic particles 4 are welded to the surfaces of the organic fibers 1 by the welded parts 5, so that the apparent fiber diameter of the organic fibers 1 becomes large, which supports the shape of the thermal insulation material 10 and provides high strength.

[0048] The welded portion 5 does not need to completely cover the outer periphery of the organic fiber 1, and there may be some areas where the welded portion 5 is not present. In the thermal insulation material 10, binder fibers having a sheath-core structure, which will be described later, can be used as the material for the organic fiber 1, but if the sheath portion peels off during the manufacturing process, the organic fiber 1, which is the core portion, may be partially exposed. Even in such a case, the effect of holding the inorganic particles 4 can be sufficiently obtained.

[0049] Furthermore, it is preferable that the thermal insulation material 10 according to the thermal insulation material (Structural Example 1) further contains inorganic fibers. The effect obtained by containing inorganic fibers will be described in the following "Thermal insulation material (Structural Example 2)".

[0050] <Thermal insulation (Structure example 2)> Fig. 5 is a photograph substituting a drawing showing a second structural example of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention. In the second structural example shown in Fig. 5, the same components as those in the first structural example shown in Fig. 3 and Fig. 4 are given the same reference numerals and detailed explanations are omitted. Note that the heat insulating material 40 shown in Fig. 5 can be used in place of the heat insulating material 10 of the heat-transfer-suppressing sheet 50 shown in Fig. 1.

[0051] As shown in Fig. 5, the heat insulating material 40 has inorganic fibers 15. The heat insulating material 40 has a fiber layer 11 formed on at least a part of a first surface 40a and a second surface (not shown) perpendicular to the thickness direction of the heat insulating material 40. The fiber layer 11 is formed by welding at least a part of a plurality of organic fibers 1 to each other at welding parts, and is formed in a layer on the surface (first surface and second surface) of the heat insulating material 40. That is, the fiber layer 11 is a layer formed by gathering 10 or more organic fibers 1 on the surface of the heat insulating material 40, and extends, for example, in stripes, in a direction approximately parallel to the surface.

[0052] Furthermore, a composite layer (not shown) containing a mixture of part of the fiber layer 11 and part of the inorganic particles 4 is formed between the fiber layer 11 and the base layer 13 containing the inorganic particles 4 and the organic fibers 1. Specifically, the composite layer is a region containing a plurality of organic fibers 1 at least partially welded to one another by welded parts, and inorganic particles 4 welded to the organic fibers 1 by welded parts.

[0053] In the heat insulating material 40 shown in Fig. 5, the inorganic fibers 15 are contained in the base layer 13 containing the inorganic particles 4 and the organic fibers 1, but may also be contained in the fiber layer 11. In Fig. 5, the inorganic fibers 15 in the fiber layer 11 cannot be distinguished, so they are not shown.

[0054] Furthermore, the thermal insulation material 40 has a fiber bundle 6 formed by at least a portion of a plurality of organic fibers 1 being welded together by a welded portion 5. The fiber bundle 6 is formed by entangling 10 or more organic fibers 1 with one another and by welding the organic fibers 1 to one another at some portions, and is arranged in an arbitrary direction in the thermal insulation material 40.

[0055] The insulating material 40 configured in this manner contains inorganic fibers 15 that are difficult to decompose even at high temperatures. Therefore, for example, if the battery cell 20a experiences thermal runaway and the heat-transfer-suppressing sheet 50 disposed adjacent to the battery cell 20a is exposed to high temperatures, even if the organic fibers 1 in the insulating material 40 decompose, the inorganic fibers 15 remain, so that the shape of the insulating material 40 can be reliably maintained. Furthermore, the flexible organic fibers 1 tend to become entangled with the relatively hard inorganic fibers 15, and the inorganic fibers 15 and the organic fibers 1 form a three-dimensional skeleton, so that the strength of the insulating material 40 can be further improved. In addition, in the "Thermal Insulation Material (Structural Example 2)", the thermal insulation material 40 has organic fibers 1 in addition to inorganic fibers 15. However, even if the thermal insulation material does not have organic fibers 1 and has only inorganic particles 4 and inorganic fibers 15, it goes without saying that the above-mentioned effect that the inorganic fibers 15 remain and the shape of the thermal insulation material 40 can be reliably maintained can be obtained.

[0056] Furthermore, when the insulating material 40 has both the organic fibers 1 and the inorganic fibers 15, it is particularly preferable because it simultaneously has the effects of "the insulating material 10 can be made more flexible because it contains the organic fibers 1, which have high flexibility, and the organic fibers 1 are more likely to entangle with each other, thereby improving the sheet strength" and "even if the organic fibers 1 in the insulating material 40 decompose when the heat transfer-suppressing sheet 50 is exposed to high temperatures, the inorganic fibers 15 remain, so the shape of the insulating material 40 can be reliably maintained."

[0057] Furthermore, when the insulation material 40 has the fiber layer 11 on its surface and the fiber bundles 6 inside, it can obtain a higher strength than when the organic fibers 1 are dispersed and arranged. The fiber layer 11 is not simply arranged on the base layer 13, but has a composite layer between the fiber layer 11 and the base layer 13 in which a part of the fiber layer 11 and a part of the inorganic particles 4 are mixed, so that the fiber layer 11 is securely bound to the surface of the insulation material 40. Therefore, the fiber layer 11 alone does not fall off, and the insulation material 40 having high strength can be obtained, and since the elastic sheet 51 is laminated on this insulation material 40, the pressure on the base layer 13 can be further reduced.

[0058] Furthermore, when a fiber layer 11 is formed on the surface of the insulation material 40, this fiber layer 11 can absorb impacts applied to the insulation material 40, and therefore, even on surfaces on which the elastic sheet 51 is not laminated, the effect of preventing the inorganic particles contained in the insulation material 40 from falling off can be obtained.

[0059] <Thermal insulation (Structure example 3)> Fig. 6 is a schematic diagram showing a third structural example of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention, and Fig. 7 is a schematic diagram showing an enlarged portion of Fig. 6. Fig. 8 is a photograph showing the heat insulating material shown in Fig. 6. In Structural Example 3 shown in Figs. 6 to 8, the same components as those in Structural Example 1 shown in Figs. 3 and 4 are given the same reference numerals and detailed explanations are omitted. Note that the heat insulating material 60 shown in Figs. 6 to 8 can be used in place of the heat insulating material 10 of the heat-transfer-suppressing sheet 50 shown in Fig. 1.

[0060] As shown in FIG. 6 to FIG. 8, the heat insulating material 60 according to this embodiment has inorganic particles 4, organic fibers 1 made of a first organic material, and a welded portion 5 covering the outer circumferential surface of the organic fibers 1. As described above, the welded portion 5 includes a second organic material 17 having a melting point lower than that of the first organic material, and inorganic particles 4. In this embodiment, a binder fiber 3 having a core-sheath structure with a core and a sheath covering the outer circumferential surface of the core is used as the organic fiber, and the organic fiber 1 corresponds to the core. The welded portion 5 is formed by melting the sheath of the binder fiber 3 having a core-sheath structure once by heating and then cooling it. Furthermore, as shown in FIG. 8, a fiber portion 16 is formed by the organic fiber 1 and the welded portion 5 including the inorganic particles 4, and a matrix portion 18 including inorganic particles is formed between the multiple fiber portions 16. When the melted sheath portion is cooled, the adjacent organic fibers 1 are fused to each other at the contact portion 31 to form a three-dimensional skeleton.

[0061] In the insulating material 60 configured in this manner, the organic fibers 1 and the welded parts 5 act as a skeleton, so that excellent strength and shape retention can be obtained. Furthermore, on both the surface side and the center side of the insulating material 60, the welded parts 5 covering the outer periphery of the organic fibers fix the inorganic particles 4 to the organic fibers 1, so that powder falling off can be suppressed. Therefore, for example, even if the heat-transfer-suppressing sheet 50 according to this embodiment is disposed between a plurality of battery cells and the battery cells expand, causing compressive stress or impact on the heat-transfer-suppressing sheet 50, excellent insulating performance can be maintained.

[0062] The mechanism by which the above-mentioned heat insulating material 60 can suppress the inorganic particles 4 from falling off (powdering) is not clear, but one of the reasons is thought to be that the organic fibers 1 and the fused parts 5 form a three-dimensional and strong skeleton, and the shape of the heat insulating material 60 is maintained, so that deformation or compression of the heat insulating material 60 is suppressed. In addition, since the elastic sheet 51 is laminated on at least one of the first and second surfaces of the heat insulating material 60, the pressure on the heat insulating material 60 is reduced, which is also thought to contribute to suppressing the inorganic particles 4 from falling off. It is to be noted that, regardless of the presence or absence of the elastic sheet 51 on the surface of the heat insulating material 60, the fiber part 16 exposed on the surface of the heat insulating material 60 can absorb impacts given to the heat insulating material 60, which is also thought to be the reason why the inorganic particles 4 are held.

[0063] 8, in the insulating material 60, the welded portion 5 does not need to completely cover the outer peripheral surface of the organic fiber 1, and the organic fiber 1 may be partially exposed. Since the insulating material 60 uses binder fiber 3 having a core-sheath structure, the sheath portion may peel off during the manufacturing process of the insulating material 60, but even if the organic fiber 1 is partially exposed, the effect of the present invention can be sufficiently obtained.

[0064] <Thermal insulation (Structure example 4)> Fig. 9 is a photograph substituting a drawing showing a fourth structural example of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention, and Fig. 10 is a photograph substituting a drawing showing an enlarged view of the structure of the heat insulating material shown in Fig. 9. Fig. 11 is a photograph substituting a drawing showing a cross section of the heat insulating material shown in Fig. 9. In Structural Example 4 shown in Figs. 9 to 11, the same components as those in Structural Example 1 shown in Figs. 3 and 4 are given the same reference numerals and detailed explanations are omitted. Note that the heat insulating material 70 shown in Figs. 9 to 11 can be used in place of the heat insulating material 10 of the heat-transfer-suppressing sheet 50 shown in Fig. 1.

[0065] 9 and 10, the heat insulating material 70 has a matrix 14 containing inorganic particles 4, and organic fibers 1 oriented three-dimensionally in this matrix 14. The organic fibers 1 have welded parts 5 covering at least a part of their surfaces, and the organic fibers 1 are welded to each other by the welded parts 5. Similarly, the inorganic particles 4 are welded to the surfaces of the organic fibers 1, so that the surfaces of the organic fibers 1 are covered with the inorganic particles 4.

[0066] As shown in the cross-sectional view of Fig. 11, a plurality of voids 7 are formed in the matrix 14 of the thermal insulation material 70. Furthermore, at least some of the organic fibers 1 in the matrix 14 are welded to each other by welded parts 5 not shown in Fig. 11 to form fiber bundles 6, and voids 8 are formed between the organic fibers 1 constituting the fiber bundles 6.

[0067] Furthermore, a fiber layer 11 is formed on at least a part of the first surface 70a and the second surface (not shown) perpendicular to the thickness direction of the heat insulating material 70. The fiber layer 11 is formed in a layer on the surface (first surface and second surface) of the heat insulating material 70 by welding at least a part of the organic fibers 1 to each other by the welding parts 5. In addition, a composite layer 12 is formed between the fiber layer 11 and the base layer 13 containing the matrix 14 and the organic fibers 1. The composite layer 12 is a layer in which a part of the fiber layer 11 and a part of the matrix 14 are mixed. Specifically, the composite layer 12 is a region including a plurality of organic fibers 1 at least a part of which are welded to each other by the welding parts 5, and inorganic particles 4 welded to the organic fibers 1 by the welding parts 5.

[0068] The fiber bundles 6 are formed by entangling 10 or more organic fibers 1 with one another and by welding the organic fibers 1 to one another in some places, and are arranged in an arbitrary direction in the matrix 14 of the thermal insulation material 70. On the other hand, the fiber layer 11 is a layer formed by assembling 10 or more organic fibers 1 on the surface of the thermal insulation material 70, and extends, for example, in stripes in a direction substantially parallel to the surface.

[0069] In the insulating material 70 configured in this manner, the organic fibers 1 are oriented three-dimensionally in the matrix 14, and the organic fibers 1 have welded parts 5 that cover at least a part of their surfaces. The welded parts 5 refer to parts where the surfaces of the organic fibers 1 are melted and then solidified again, and are formed during the manufacturing process of the insulating material 70. In the insulating material 70, the three-dimensionally oriented organic fibers 1 are welded to each other by the welded parts 5, and this structure serves as a skeleton to support the shape of the insulating material 70, thereby achieving high strength.

[0070] Similarly, in the thermal insulation material 70, the welded portion 5 on the outer peripheral surface of the organic fibers 1 also fixes the inorganic particles 4 to the organic fibers 1, thereby achieving an even greater powder-fall suppression effect. Therefore, for example, even if a portion of the battery cells 20a, 20b, and 20c expands during charging and discharging, causing compressive stress or impact on the heat-transfer-suppressing sheet 50, the shape of the thermal insulation material 70 can be maintained. As a result, it is possible to suppress the inorganic particles 4 from falling off (powdering), and to prevent a decrease in the insulating effect of the thermal insulation material 70 due to compressive deformation.

[0071] The mechanism by which the insulating material 70 can prevent the inorganic particles 4 from falling off from the sheet surface is believed to be similar to that of the insulating material 60 of Structural Example 3 above.

[0072] In the heat insulating material 70, the welded parts 5 do not need to completely cover the outer circumferential surface of the organic fibers 1, and there may be some areas where the welded parts 5 are not present. Even in such a case, the effect of holding the inorganic particles 4 can be sufficiently obtained.

[0073] Furthermore, since the insulating material 70 contains organic fibers 1 that have high flexibility, the flexibility of the insulating material 70 can be increased and the organic fibers 1 can be easily entangled with each other, which has the effect of improving the sheet strength.

[0074] Furthermore, the heat insulating material 70 has a plurality of pores 7 in the matrix 14 and voids 8 between the plurality of organic fibers 1 constituting the fiber bundle 6, thereby improving the heat insulating performance. Also, due to the presence of the voids 8, the organic fibers 1 are less likely to be constrained in the matrix 14, so that the flexibility and strength of the heat insulating material 70 can be further improved. The voids 8 do not need to be formed in the entire area between the plurality of organic fibers 1, and as long as the voids 8 are formed in at least a portion of the areas between the organic fibers 1, the effect of suppressing heat transfer can be obtained.

[0075] Furthermore, since the insulating material 70 has the fiber bundles 6 and the fiber layer 11, it is possible to obtain a much higher strength than when the organic fibers 1 are arranged in a dispersed manner. Moreover, the fiber layer 11 is not simply arranged on the base layer 13, but has a composite layer 12 between the fiber layer 11 and the base layer 13 in which a part of the fiber layer 11 and a part of the inorganic particles 4 constituting the matrix 14 are mixed, so that the fiber layer 11 is securely bound to the surface of the insulating material 70. Therefore, it is possible to obtain an insulating material 70 having high strength.

[0076] <Thermal insulation (Structure example 5)> Fig. 12 is a schematic diagram showing a fifth structural example of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention, and Fig. 13 is a schematic diagram showing an enlarged view of part A of the heat insulating material shown in Fig. 12. In Structural example 5 shown in Figs. 12 and 13, the same components as those in structural example 1 of the heat insulating material shown in Figs. 3 and 4 are given the same reference numerals and detailed explanations are omitted. Note that the heat insulating material 80 shown in Figs. 12 to 13 can be used in place of the heat insulating material 10 of the heat-transfer-suppressing sheet 50 shown in Fig. 1.

[0077] As shown in Figs. 12 and 13, the heat insulating material 80 has a matrix 14 containing inorganic particles 4, inorganic fibers 15 dispersed in the matrix 14, and organic fibers 1. The organic fibers 1 and the inorganic fibers 15 are entangled with each other to form a three-dimensional web structure. In this embodiment, an air layer 28 is formed in a part around the inorganic fibers 15. The organic fibers 1 have a welded portion 5 on a part of their surface, and at least a part of the inorganic fibers 15 is welded to the organic fibers 1 by the welded portion 5. Furthermore, at least a part of the inorganic particles 4 is welded to the organic fibers 1 by the welded portion 5.

[0078] In this specification, the term "dispersed" of the inorganic fibers 15 refers to a state in which the inorganic fibers 15 are not distributed unevenly, but are spread out over the entire surface.

[0079] In the insulating material 80 configured in this manner, the organic fibers 1 and the inorganic fibers 15 are intertwined with each other to form a three-dimensional web structure, and this structure serves as the skeleton, thereby providing high strength. Therefore, even if the heat-transfer-suppressing sheet 50 is compressed due to the expansion of the battery cells 20a, 20b, and 20c during charging and discharging, the shape of the insulating material 80 can be maintained. As a result, it is possible to suppress the inorganic particles 4 from falling off (powdering), and to prevent a decrease in the insulating effect of the insulating material 80 due to compression deformation.

[0080] Furthermore, since the heat insulating material 80 contains the organic fibers 1 having high flexibility, the flexibility of the heat insulating material 80 can be increased, and the organic fibers 1 are easily entangled with the inorganic fibers 15 to form a three-dimensional web structure, thereby improving the strength. Furthermore, if the heat insulating material 80 contains the inorganic fibers 15, for example, when the battery cell 20a experiences thermal runaway and the heat-transfer-suppressing sheet disposed adjacent to the battery cell 20a is exposed to high temperatures, the shape of the heat-transfer-suppressing sheet can be maintained even if the organic fibers 1 are decomposed. Therefore, by having the heat insulating material 80 contain the organic fibers 1 having high flexibility and the inorganic fibers 15 that do not decompose even at high temperatures, it is possible to obtain a heat-transfer-suppressing sheet that has a good balance between flexibility and strength.

[0081] Furthermore, in this embodiment, an air layer 28 is provided around the inorganic fibers 15 dispersed in the matrix 14. The inorganic fibers 15 have a higher thermal conductivity than the organic fibers 1, but as described above, the air layer 28 is formed around the inorganic fibers 15, thereby suppressing heat transfer between the inorganic fibers 15 and the matrix 14. The air layer 28 is formed in the manufacturing process of the heat insulating material 80, but it is not necessary for the air layer 28 to be formed around the entire area around the inorganic fibers 15. As long as the air layer 28 is formed on at least a part of the outer circumferential surface of the inorganic fibers 15, the effect of suppressing heat transfer can be obtained. When the inorganic fibers 15 are uniformly dispersed in the matrix 14, the air spaces 28 in the matrix 14 are also uniformly dispersed and disposed, so that the heat insulating material 80 can obtain high heat insulating properties without unevenness.

[0082] Furthermore, in the insulating material 80, the organic fibers 1 have welded parts 5 covering at least a part of the surface. The welded parts 5 refer to parts where the surfaces of the organic fibers 1 melt and then solidify again, and are formed during the manufacturing process of the insulating material 80. When at least a part of the inorganic fibers 15 is welded to the organic fibers 1 by the welded parts 5, the entangled organic fibers 1 and the inorganic fibers 15 are fixed, so that an insulating material 80 with even higher strength can be obtained.

[0083] Similarly, in this embodiment, the welded portion 5 on the outer peripheral surface of the organic fiber 1 also fixes the inorganic particles 4 to the organic fiber 1, thereby achieving an even greater powder fall-prevention effect. Therefore, for example, even if a portion of the battery cells 20a, 20b, 20c expands and applies a compressive stress or impact to the heat-transfer-suppressing sheet, excellent heat insulating performance can be maintained.

[0084] In this embodiment, the mechanism by which the inorganic particles 4 can be prevented from falling off from the sheet surface is believed to be that the organic fibers 1 and the inorganic fibers 15 are welded to each other by the welded parts 5 to form a three-dimensional, strong skeleton, which maintains the shape of the heat insulating material 80 and prevents deformation or compression of the heat-transfer-suppressing sheet. Furthermore, regardless of the presence or absence of the elastic sheet 51 on the surface of the heat insulating material 80, when the organic fibers 1 and the inorganic fibers 15 are exposed on the surface of the heat insulating material 80, it is believed that the impact given to the heat insulating material 80 can be absorbed and the inorganic particles 4 are held in place.

[0085] In the heat insulating material 80, the welded parts 5 do not need to completely cover the outer circumferential surface of the organic fibers 1, and there may be some areas where the welded parts 5 are not present. Even in such a case, the effect of holding the inorganic particles 4 can be sufficiently obtained.

[0086] <Thermal insulation (Structure example 6)> Fig. 14 is a photograph substituting a drawing showing a sixth structural example of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention, and Fig. 15 is a photograph substituting a drawing showing another region of the heat insulating material shown in Fig. 14. Fig. 16 is a photograph substituting a drawing showing a cross section of the heat insulating material shown in Figs. 14 and 15. In Structural Example 6 shown in Figs. 14 to 16, the same components as those in Structural Example 4 of the heat insulating material shown in Figs. 9 to 11 are given the same reference numerals and detailed description will be omitted. Note that the heat insulating material 90 shown in Figs. 14 to 16 can be used in place of the heat insulating material 10 of the heat-transfer-suppressing sheet 50 shown in Fig. 1.

[0087] 14, the heat insulating material 90 includes inorganic particles 4 and organic fibers 1. At least some of the organic fibers 1 have a branched structure including a base 32 and branches 33 extending from the base 32. In this embodiment, the branches 33 extend from the base 32 in four directions, namely, directions D1, D2, D3, and D4. The base 32 and the multiple branches 33 form a skeleton.

[0088] 15 also contains organic fibers 1 having a branched structure consisting of a base 32 and branches 33 extending from the base 32. The organic fibers 1 shown in Fig. 15 have a base 32 and branches 33 extending from the base 32 in five directions, namely, directions D1, D2, D3, D4, and D5, and the base 32 is thicker than the multiple branches 33.

[0089] Furthermore, in this embodiment, as shown in FIGS. 14 and 15, inorganic particles 4 are fused to the surface of the organic fiber 1, so that the surface of the organic fiber 1 is covered with the inorganic particles 4.

[0090] As shown in the cross-sectional view of Fig. 16, a plurality of voids 7 are formed in the heat insulating material 90. Furthermore, in the heat insulating material 90, a fiber bundle 6 is formed by at least partially fusing a plurality of organic fibers 1 together, and voids 8 are formed between the plurality of organic fibers 1 constituting the fiber bundle 6. Note that, also in Fig. 16, it is possible to confirm the organic fibers 1 having a branched structure consisting of a base 32 and branches 33 extending in three directions from the base 32.

[0091] Furthermore, a fiber layer 11 may be formed on at least a part of the first surface and the second surface perpendicular to the thickness direction of the heat insulating material 90. The fiber layer 11 is formed in a layer on the surface (first surface and second surface) of the heat insulating material 90 by welding at least a part of the organic fibers 1 to each other. In addition, a composite layer 12 may be formed between the fiber layer 11 and the base layer 13 containing the inorganic particles 4 and the organic fibers 1. The composite layer 12 is a layer in which a part of the fiber layer 11 and a part of the inorganic particles 4 are mixed. Specifically, the composite layer 12 is a region containing a plurality of organic fibers 1 welded to each other and the inorganic particles 4 welded to the organic fibers 1.

[0092] The fiber bundles 6 are formed by entangling 10 or more organic fibers 1 with one another and by welding the organic fibers 1 to one another in some places, and are arranged in an arbitrary direction inside the thermal insulation material 90. On the other hand, the fiber layer 11 is a layer formed by assembling 10 or more organic fibers 1 on the surface of the thermal insulation material 90, and extends, for example, in stripes in a direction substantially parallel to the surface.

[0093] In the heat insulating material 90 configured in this manner, at least a portion of the organic fibers 1 has a branched structure consisting of a base 32 and a branch 33, and therefore the organic fibers 1 serve as a skeleton to maintain the shape of the heat insulating material 90. In this embodiment, the base 32 is configured by a fused portion in which the organic fibers 1 are fused to each other. Specifically, the base 32 is a portion in which a plurality of organic fibers 1 are brought into contact with each other, melted together, and then solidified, and is therefore thicker than the branch 33. Therefore, the entire skeleton can be firmly supported by the base 32, and the strength of the heat insulating material 90 can be significantly improved.

[0094] In the thermal insulation material 90, at least a part of the organic fibers 1 has a branched structure consisting of a base 32 and branches 33 extending from the base 32 in at least three directions. The branched structure can be confirmed in a cross-sectional photograph of the thermal insulation material 90, but an easier way to confirm the branched structure is to observe a cross-section of the thermal insulation material 90 torn in a plane direction perpendicular to its thickness direction. In this way, by observing the cross-section, it is possible to easily confirm that the organic fibers 1 have a branched structure consisting of a base 32 and branches 33 extending from the base 32 in at least three directions. The base 32 and the branches 33 will be described in more detail below.

[0095] (Base (fusion part)) The fused portion is formed when the sheath portion of the binder fiber is heated and melted once and then cooled in a portion where a plurality of binder fibers are in contact with each other when a binder fiber with a core-sheath structure is used as the material of the thermal insulation material 90. When a binder fiber with a core-sheath structure is used as the material of the thermal insulation material 90, the fused portion contains the second organic material that constitutes the sheath portion. Thus, in the manufacturing process of the heat-transfer-suppressing sheet 50, when the sheath in the region where multiple binder fibers are in contact is melted by heating, the amount of melted sheath (second organic material) is greater than when the sheath of a single binder fiber is melted, and a thick fused portion (base 32) is formed after cooling. As a result, the skeleton is firmly supported by the base 32.

[0096] (branch) The support parts 33 extend in at least three directions from the base part 32 and have the effect of holding the inorganic particles 4. Furthermore, the base part 32 and the support parts 33 form a skeleton, which can also improve the strength of the heat-transfer-suppressing sheet 50. This makes it possible to obtain a high powder-fall suppression effect. When a binder fiber having a core-sheath structure is used as the organic fiber 1, the branch 33 is a part of the binder fiber having a core-sheath structure, and has a core made of a first organic material and a sheath made of a second organic material.

[0097] As long as the branches 33 extending from the base 32 extend in at least three directions, a skeleton made of the organic fibers 1 can be formed. In addition, it is preferable that these multiple branches 33 each extend in a different three-dimensional direction, which allows a three-dimensional, strong skeleton to be formed.

[0098] In the above-mentioned insulating material 90, since a plurality of support parts 33 extend from the base part 32, the inorganic particles 4 can be held by these support parts 33, and a high powder-fall suppression effect can be obtained by a synergistic effect with the effect of improving the sheet strength by forming a skeleton. Therefore, for example, even if a portion of the battery cells 20a, 20b, and 20c expands during charging and discharging, causing compressive stress or impact on the heat-transfer-suppressing sheet, the shape of the insulating material 90 can be maintained. As a result, it is possible to suppress the inorganic particles 4 from falling off (powder falling off), and to prevent a decrease in the insulating effect of the insulating material 90 due to compressive deformation.

[0099] The mechanism by which the inorganic particles 4 can be prevented from falling off from the surface of the insulating material 90 is thought to be due to the fact that, in addition to the same effect as the insulating material 60 of Structural Example 3 above, the support parts 33 also have a holding effect on the inorganic particles 4. Furthermore, when the inorganic particles 4 are fused to the surface of the organic fibers 1, the organic fibers 1 appear to have a thicker fiber diameter, so that the strength is higher than that of the organic fibers 1 alone, and a high holding effect on the inorganic particles 4 can be obtained.

[0100] In the heat insulating material 90, there may be a region where the inorganic particles 4 are not partially welded to the outer peripheral surface of the organic fibers 1. Even in such a case, the effect of holding the inorganic particles 4 can be sufficiently obtained.

[0101] Furthermore, since the insulating material 90 contains organic fibers 1 that have high flexibility, the flexibility of the insulating material 90 can be increased and the organic fibers 1 can be easily entangled with each other, which has the effect of improving the sheet strength.

[0102] Furthermore, the heat insulating material 90 preferably has a plurality of pores 7 and also has gaps 8 between the plurality of organic fibers 1 constituting the fiber bundle 6, thereby obtaining the effect of air insulation and improving the heat insulating performance. Also, due to the presence of the gaps 8, the organic fibers 1 are not completely restrained, so that the flexibility and strength of the heat insulating material 90 can be further improved. The gaps 8 do not need to be formed in the entire area between the plurality of organic fibers 1, and as long as the gaps 8 are formed in at least a portion of the organic fibers 1, the effect of suppressing heat transfer can be obtained.

[0103] Furthermore, since the insulating material 90 has the fiber bundles 6 and the fiber layer 11, it is possible to obtain a sheet strength that is even higher than when the organic fibers 1 are arranged in a dispersed manner. Furthermore, when the fiber layer 11 is present, the fiber layer 11 is not simply arranged on the base layer 13, but has a composite layer 12 between the fiber layer 11 and the base layer 13 in which part of the fiber layer 11 and part of the inorganic particles 4 are mixed, so that the fiber layer 11 is securely bound to the surface of the insulating material 90. Therefore, the strength of the insulating material 90 can be improved.

[0104] <Thermal insulation (Structure example 7)> Fig. 17 is a photograph substituting a drawing showing a seventh structural example of a heat insulating material used in a heat-transfer-suppressing sheet according to an embodiment of the present invention, and Fig. 18 is a photograph substituting a drawing showing an enlarged portion of the heat insulating material shown in Fig. 17. In Structural example 7 shown in Figs. 17 and 18, the same components as those in structural example 2 of the heat insulating material shown in Fig. 5 are given the same reference numerals and detailed explanations are omitted. Note that the heat insulating material 110 shown in Figs. 17 and 18 can be used in place of the heat insulating material 10 of the heat-transfer-suppressing sheet 50 shown in Fig. 1.

[0105] 17 and 18, the thermal insulation material 110 has inorganic particles 4 and organic fibers 1. A first region 42 having streak-like fiber bundles 47 made of a plurality of organic fibers 1 and a second region 43 in which no fiber bundles 47 are present are formed on the surface of the thermal insulation material 110. In this specification, the fiber bundles 47 are 10 or more organic fibers 1 intertwined with each other, and extend in a streak-like manner in a direction approximately parallel to the surface of the thermal insulation material 110.

[0106] That is, when the surface of the thermal insulation material 110 is observed, a state in which a plurality of organic fibers 1 are entangled is observed in the first region 42, as shown in Fig. 18. On the other hand, in the second region 43, although there are some places where a few organic fibers 1 are observed, fiber bundles 47 in which a plurality of organic fibers 1 are entangled are not observed. In this embodiment, the first region 42 and the second region 43 have a sea-island structure, and the second region 43 corresponding to an island portion is formed so as to be surrounded by the first region 42 corresponding to a sea portion.

[0107] In the heat insulating material 110, fiber bundles 47 in which the organic fibers 1 are entangled are present so as to extend like stripes on the surface of the heat insulating material 110, and therefore the strength of the heat insulating material 110 can be improved. Also, since the entire surface is not covered with the fiber bundles 47, but there is a first region 42 where the fiber bundles 47 are present and a second region where the fiber bundles 47 are not present, the flexibility of the heat insulating material 110 is also excellent. Furthermore, since the fiber bundles 47 are present on the surface of the heat insulating material 110, even if the heat insulating material 110 is subjected to an impact or pressure, the fiber bundles 47 can absorb and mitigate the impact or pressure. Therefore, it is possible to suppress the inorganic particles 4 from falling off (powdering), and it is possible to prevent a decrease in the heat insulating performance of the heat insulating material 110.

[0108] In the heat insulating material 110, the organic fibers 1 and the fiber bundles 47 in which the organic fibers 1 are entangled are present not only on the surface of the heat insulating material 110 but also inside the heat insulating material 110. This makes it possible to obtain even greater strength.

[0109] It is preferable that the length of the fiber bundles 47 formed so as to extend over the surface of the heat insulating material 110 is relatively long. An example of a method for determining the length of the fiber bundles 47 will be described with reference to FIG. 19, rectangular imaginary frames 21 are arranged along the streak-like fiber bundles 47 on the surface of the thermal insulation material 110. In this embodiment, the size of the imaginary frames 21 is 5 mm square, and these imaginary frames 21 are arranged so as to be continuous with each other. In this case, if there are fiber bundles 47 that penetrate at least three continuous imaginary frames 21, it can be determined that the effect of improving the strength of the thermal insulation material 110 is sufficient.

[0110] It is also possible to simply measure the length of the fiber bundles 47 extending in a stripe shape. For example, a method can be used in which a string or the like is placed on the surface of the thermal insulation material 110 along the fiber bundles 47, and then the length of the string is measured. When the length of continuous fiber bundles 47 is measured, if there are fiber bundles 47 with a length of 20 mm or more, the effect of improving the strength of the thermal insulation material 110 can be sufficiently obtained.

[0111] Furthermore, as shown in FIG. 20, if the fiber bundles 47 are connected in a mesh pattern on the surface of the heat insulating material 110, the sheet strength can be further improved.

[0112] Although the insulating material has been described above with reference to structural examples 1 to 7, the structure of the insulating material is not limited thereto, and insulating materials having various structures can be used. Specifically, the insulating materials of structural examples 1 to 7 have excellent insulating effect and also have various properties such as the effect of suppressing powder falling, the effect of further improving strength, and the effect of maintaining shape. Therefore, as shown in FIG. 1, a heat-transfer-suppressing sheet 50 in which an elastic sheet 51 is laminated on the insulating material can obtain the various effects described above and can prevent unnecessary pressure from being applied to the battery cells 20a, 20b, and 20c.

[0113] [Second embodiment] The heat-transfer-suppressing sheet according to the present embodiment preferably has a film covering the outer peripheral surface. A heat-transfer-suppressing sheet having a film will be described below with reference to the drawings. Fig. 21A is a perspective view showing a heat-transfer-suppressing sheet according to a second embodiment of the present invention, and Fig. 21B is a cross-sectional view thereof.

[0114] As shown in FIG. 21A and FIG. 21B, the heat transfer suppressing sheet 120 according to the second embodiment includes the heat insulating material 10 shown in FIG. 1B, an elastic sheet 51 laminated on the first surface 10a side and the second surface 10b side of the heat insulating material 10, and a resin film 112 enclosing the laminate 111. The resin film 112 has a plurality of elliptical holes 113 formed therein. The resin film 112 is also composed of two main surfaces perpendicular to the thickness direction of the laminate 111, that is, a first surface side film 112a and a second surface side film 112b covering the first surface 111a and the second surface 111b of the laminate, respectively, and an end surface side film 112c covering four end surfaces 111c parallel to the thickness direction of the laminate 111. The area ratio of the holes 113 in the first surface side film 112a and the second surface side film 112b is designed to be larger than the area ratio of the holes in the end surface side film 112c.

[0115] Here, the area ratio of the holes 113 in the first surface side film 112a and the second surface side film 112b refers to the ratio of the area of ​​the holes 113 formed in the first surface side film 112a and the second surface side film 112b to the total area of ​​the first surface side film 112a and the second surface side film 112b. Also, the area ratio of the holes in the end surface side film 112c refers to the ratio of the area of ​​the holes formed in the end surface side film 112c to the total area of ​​the end surface side film 112c.

[0116] In the second embodiment, the laminate 111 is wrapped in a planar resin film, and the resin films 112 are fused together near the end faces 111c of the laminate 111 to form the film fused portion 114. The resin film 112 is heated and contracted, so that the laminate first face 111a, laminate second face 111b, and end faces 111c of the laminate 111 are covered with the resin film 112, and are in close contact with the surface of the laminate 111. Therefore, since the film fused portion 114 is mainly formed in the end face side film 112c, the thickness of the region where the film fused portion 114 is formed is increased, and as a result, the end face side film 112c has a higher strength than the first face side film 112a and the second face side film 112b. Furthermore, even if holes 113 are present on the end face 111c of the laminate 111 when the laminate 111 is wrapped in a planar resin film, the formation of the film fused portion 114 causes the area ratio of the holes 113 in the end face side film 112c to be smaller than the area ratio of the holes 113 in the first surface side film 112a and the second surface side film 112b.

[0117] A specific example of application of the heat-transfer-reducing sheet 120 configured as described above to a battery pack will be described below. Here, the case where the heat-transfer-reducing sheet 120 shown in Fig. 21A and Fig. 21B is applied instead of the heat-transfer-reducing sheet 50 of the battery pack 100 shown in Fig. 2 will be described.

[0118] In the heat-transfer-suppressing sheet 120 according to the second embodiment, the laminate 111 is encapsulated in a resin film, which makes it possible to prevent particles and the like from falling off when the heat-transfer-suppressing sheet 120 is incorporated into the battery pack 100. Furthermore, the elastic sheet 51 has a predetermined elasticity, and when the heat-transfer-suppressing sheet 120 is pressed due to the expansion of the battery cells 20a, 20b, and 20c, the elastic sheet 51 deforms by an appropriate amount, thereby suppressing the repulsive force on the battery cells. This makes it possible to suppress a decrease in battery performance caused by repeated pressing and relaxing of the battery cells 20a, 20b, and 20c.

[0119] Furthermore, since the insulating material 10 constituting the laminate 111 contains inorganic particles and organic fibers and has high thermal insulation properties, it is possible to suppress the transfer of heat from a battery cell that has experienced thermal runaway to adjacent battery cells. Furthermore, when the heat-transfer-suppressing sheet 120 is incorporated into the battery pack 100, it is possible to prevent misalignment between the insulating material 10 and the elastic sheet 51.

[0120] Also, for example, when the temperature of the battery cell 20a rises, the air contained in the inside of the heat insulating material 10 in the laminate 111 arranged between the battery cell 20a and the battery cell 20b, and between the laminate 111 and the resin film 112, etc. expands, and the air is discharged from the holes 113 of the resin film 112. At this time, in the second embodiment, for example, the area ratio of the holes 113 in the first surface side film 112a and the second surface side film 112b that are in contact with the battery cells 20a and 20b is larger than the area ratio of the holes 113 in the end surface side film 112c. Therefore, air is easily discharged from the first surface side film 112a and the second surface side film 112b. As a result, air is slowly discharged from the gap between the battery cells 20a and 20b and the heat transfer suppressing sheet 120 through the holes 113 of the first surface side film 112a and the second surface side film 112b, so that the spread of particle contamination in the battery case 30 can be suppressed.

[0121] In order to exhaust more air from the holes 113 in the first surface side film 112a and the second surface side film 112b, it is preferable that the area ratio of the holes 113 in the end surface side film 112c is as small as possible, and it is more preferable that the end surface side film 112c has no holes (i.e., an area ratio of 0%). Even if the end surface side film 112c has holes 113, it is preferable that the average area per hole 113 in the first surface side film 112a and the second surface side film 112b is larger than the average area per hole 113 in the end surface side film 112c.

[0122] As a method for making the area ratio of the holes 113 in the end surface side film 112c smaller than the area ratio of the holes 113 in the first surface side film 112a and the second surface side film 112b, a method of forming holes only in the area corresponding to the first surface side film 112a and the second surface side film 112b during the manufacture of the heat transfer suppressing sheet can be mentioned. Other methods include a method of forming holes in the area corresponding to the first surface side film 112a and the second surface side film 112b larger than holes in the area corresponding to the end surface side film 112c, and a method of forming a film fusion part 114 in which resin films are fused together in the end surface side film 112c. By forming the film fusion part 114 in the end surface side film 112c, the smoothness of the first surface side film 112a and the second surface side film 112b can also be ensured. However, depending on the manufacturing conditions, etc., a part of the film fusion part 114 may be formed in the first surface side film 112a and the second surface side film 112b. However, if most of the film fusion portion 114 is formed in the end surface side film 112c, it is possible to obtain the effect of controlling the area ratio of the holes and the effect of ensuring the smoothness of the first surface side film 112a and the second surface side film 112b.

[0123] For example, the battery cell 20a and the heat-transfer-suppressing sheet 120, and the battery cell 20b and the heat-transfer-suppressing sheet 120 are not disposed in complete contact with each other, but rather there are areas where they are in contact with each other and areas where they are slightly separated from each other. If the hole 113 were completely blocked by the area where they are in contact with each other, it would be difficult for air to be discharged from the hole 113, and the effective area ratio of the hole 113 in the first-surface-side film 112a and the second-surface-side film 112b would decrease. Therefore, in order to prevent the hole 113 from being completely blocked by an adjacent battery cell, it is preferable that the shape of the hole 113 be an ellipse that extends long in one direction.

[0124] Furthermore, when the laminate first surface 111a and the laminate second surface 111b of the laminate 111 are rectangular in shape, if the holes 113 are elliptical in shape with their major axis in the same direction as the longitudinal direction of the laminate first surface 111a and the laminate second surface 111b, adjacent holes 113 are too close to each other, reducing the strength and preventing cracks from occurring in the resin film 112. Similarly, when the holes 113 in the first surface side film 112a and the second surface side film 112b are arranged at equal intervals on the laminate first surface 111a and the laminate second surface 111b, it is possible to prevent adjacent holes 113 from being too close to each other, which would cause cracks to occur in the resin film 112. Furthermore, when the holes 113 are arranged along the longitudinal direction and the direction perpendicular to the longitudinal direction on the laminate first surface 111a and the laminate second surface 111b, it is possible to further prevent cracks from occurring.

[0125] In the second embodiment, the laminate 111 may be one in which the elastic sheet 51 is laminated on at least one of the first surface 10a and the second surface 10b of the heat insulating material 10. As shown in FIG. 1A, the elastic sheet 51 may be laminated only on the first surface 10a of the heat insulating material 10, or the elastic sheet 51 may be laminated on the first surface 10a and the second surface 10b of the heat insulating material 10. The elastic sheet 51 may be sandwiched between a pair of heat insulating materials 10, or the heat insulating material 10 may be sandwiched between a pair of elastic sheets 51. Furthermore, various sheets other than the heat insulating material and the elastic sheet 51 may be laminated. For the heat insulating material 10, any of the heat insulating materials 10, 40, 60, 70, 80, 90, and 110 of the above-mentioned structural examples 1 to 7 may be used, and the effects specific to each heat insulating material can be obtained.

[0126] As shown in the above-mentioned insulating material 10, insulating material 70, and insulating material 90, when a plurality of pores 7 or voids 8 are formed, it is preferable that the pores 7 or voids 8 communicate with the holes 113 of the resin film 112, because this facilitates the air in the insulating material to be discharged through the holes 113. Furthermore, when inorganic hydrate particles are contained as inorganic particles in the insulating material 10, when the insulating material 10 is thermally decomposed by heating and releases water of crystallization, the water of crystallization is easily discharged from the holes 113 of the resin film 112 through the pores 7 or voids 8.

[0127] Furthermore, in the second embodiment, air is more easily discharged from the first surface side film 112a and the second surface side film 112b than from the end surface side film 112c, which further prevents inorganic particles, etc., which are the material of the insulating material 10, from being ejected into the inside of the battery case 30 and causing the spread of contamination.

[0128] [Third embodiment] Fig. 23A is a top view showing a heat-transfer-suppressing sheet according to a third embodiment of the present invention, and Fig. 23B is a cross-sectional view taken along line II of Fig. 23A. A heat-transfer-suppressing sheet 130 according to the first embodiment has, for example, a thermal insulator 10 containing inorganic particles, an elastic sheet 51 laminated on the first surface 10a side of the thermal insulator 10, a resin film 312 enclosing a laminate 311 of these, and a covering material 313 laminated on the resin film 312. The laminate 311 has a pair of laminate main surfaces 311a perpendicular to the thickness direction of the laminate, and two pairs of opposing laminate end surfaces 311c substantially parallel to the thickness direction.

[0129] The resin film 312 has a main surface side portion 312a located on the laminate main surface 311a side of the laminate 311, and end surface side portions 312b, 312c covering the laminate end surfaces 311b, 311c sides, and covers the entire surface of the laminate 311. In the third embodiment, a heat-shrinkable resin film 312 is used, and the resin film 312 is heat-shrinked (shrink-wrapped) to adhere to the surface of the laminate 311. At this time, a plurality of first holes 314 are formed in the main surface side portion 312a of the resin film 312 to discharge air in the internal region contained in the resin film 312 to the outside. The resin films 312 are fused to each other at the end surface sides 312b, 312c, thereby forming a fused portion 316.

[0130] A covering material 313 is laminated on the outer surface of the main surface side portion 312a of the resin film 312, and the covering material 313 and the resin film 312 are adhered to each other with an adhesive. As a result, at least a part of the first hole 314 is covered by the covering material 313.

[0131] A specific example of application of the heat-transfer-reducing sheet 130 configured as described above to a battery pack will be described below. Here, the case where the heat-transfer-reducing sheet 130 shown in Fig. 23A and Fig. 23B is applied instead of the heat-transfer-reducing sheet 50 of the battery pack 100 shown in Fig. 2 will be described.

[0132] In the third embodiment, since the laminate 311 is encapsulated in the resin film 312, it is possible to prevent particles from falling off when the heat-transfer-suppressing sheet 130 is incorporated into the battery pack 100 or when the battery pack 100 is in use, and it is also possible to prevent the laminate 311 from shifting in position. Furthermore, the heat insulating material 10 constituting the laminate 311 contains inorganic particles and has high heat insulating properties, so that it is possible to suppress the transfer of heat from a battery cell that has experienced thermal runaway to an adjacent battery cell. Furthermore, as in the second embodiment, the elastic sheet 51 can suppress the deterioration of battery performance.

[0133] Furthermore, according to the third embodiment, since the first hole 314 of the resin film 312 is covered with the covering material 313, even if the temperature inside the battery case changes and the atmosphere becomes high humidity, the heat insulating material 10 can be prevented from absorbing moisture. Therefore, the heat insulating property of the heat insulating material 10 can be prevented from decreasing.

[0134] In the third embodiment, the covering material 313 and the resin film 312 are bonded with an adhesive. However, if the surface of the resin film 312 is not completely smooth, a gap 317 may be formed between the covering material 313 and the resin film 312. When the laminate 311 is covered with the resin film 312 by shrink wrapping, a first hole (not shown) may also be formed in the end surface side portion 312c of the resin film 312 depending on the manufacturing method. In such a case, the internal region enclosed in the resin film 312 and the external region of the heat-transfer-suppressing sheet 130 are at least partially in communication with each other through the first hole 314 and the gap 317, or through the first hole 314, etc. As a result, when the heat-transfer-suppressing sheet 130 is heated to a high temperature due to an increase in the temperature of the battery cells 20a, 20b, and 20c, the gas inside can be discharged to the outside.

[0135] On the other hand, in the third embodiment, when the covering material 313 and the resin film 312 are completely adhered to each other without any gaps and further when no holes are formed in the end face side portion 312c of the resin film 312, it is possible to completely prevent moisture in the battery case 30 from penetrating into the heat transfer-inhibiting sheet 130.

[0136] In this embodiment, the covering material 313 having a size equivalent to that of the main surface side portion 312a of the resin film 312 is arranged by adhering it on the main surface side portion 312a of the resin film 312, but the position and size of the covering material 313 are not limited thereto. For example, the covering material 313 having a size smaller than that of the main surface side portion 312a may be adhered to at least a part of the area of ​​the main surface side portion 312a of the resin film 312. However, if there is a step between the resin film 312 and the covering material 313, the contact surface with the battery cells 20a, 20b, 20c may have an uneven shape, which may affect the battery performance. Therefore, it is preferable to arrange the covering material 313 having a size substantially the same as that of the main surface side portion 312a or a size larger than that of the main surface side portion 312a so that at least the entire surface of the main surface side portion 312a of the resin film 312 can be covered with the covering material 313. Here, "substantially the same" means that a difference in size between the two is acceptable up to ±5% of the average value of the two, preferably up to ±3%, and more preferably up to ±1%.

[0137] Alternatively, the covering material 313 may be disposed between the laminate 311 and the resin film 312. Furthermore, the covering material 313 may be disposed so as to surround the pair of main surface side portions 312a and the pair of end surface side portions 312c of the resin film 312, which makes it possible to cover all of the first holes 314 in the resin film 312 with the covering material 313. Furthermore, the covering material 313 may be disposed between the laminate 311 and the resin film 312. However, in order to obtain a sufficient effect of suppressing the intrusion of moisture into the internal region enclosed in the resin film 312, it is preferable that the covering material 313 is disposed so as to cover the outer surface of the resin film 312.

[0138] [Fourth embodiment] Fig. 24A is a top view showing a heat-transfer-suppressing sheet according to a fourth embodiment of the present invention, and Fig. 24B is a cross-sectional view taken along line II-II thereof. In the fourth embodiment shown in Figs. 24A and 24B, the same components as those in the third embodiment shown in Figs. 23A and 23B are given the same reference numerals, and detailed descriptions thereof will be omitted or simplified. Moreover, the fusion portion 316 shown in Figs. 23A and 23B is omitted in Figs. 24A and 24B. Hereinafter, a heat-transfer-suppressing sheet 140 according to the fourth embodiment will be described as being applied to the battery pack 100 shown in Fig. 2.

[0139] As shown in FIGS. 24A and 24B, in a heat transfer-suppressing sheet 140 according to the fourth embodiment, a laminate main surface 311a and laminate end surfaces 311b, 311c of a laminate 311 are covered with a resin film 312 by shrink packaging. Furthermore, a main surface side portion 312a and end surface side portions 312b, 312c of the resin film 312 are covered with a covering material 323 by shrink packaging. A plurality of second holes 315 are formed in the main surface side portion 323a of the covering material 323 in order to discharge internal air to the outside when the covering material 323 is shrink packaged. Furthermore, when viewed in the stacking direction of the resin film 312 and the covering material 323, i.e., when viewed from the top as shown in FIG. 24A, at least some of the plurality of second holes 315 are disposed at positions offset from the plurality of first holes 314.

[0140] Even in the fourth embodiment configured in this manner, since the laminate 311 is covered with the resin film 312, powder falling and displacement can be suppressed. Furthermore, the elastic sheet 51 constituting the laminate 311 can suppress deterioration of the battery performance. Furthermore, the first hole 314 and the second hole 315 are formed at positions shifted from each other, and the first hole 314 of the resin film 312 is covered with the covering material 323, so that the surface of the laminate 311 is not exposed. Therefore, it is possible to suppress the infiltration of moisture into the insulating material 10 constituting the laminate 311, and suppress the deterioration of the insulating properties.

[0141] In the fourth embodiment, the covering material 323 and the resin film 312 are not completely bonded to each other, and the covering material 323 is made of a heat-shrinkable film, which is heated and shrunk to adhere to the resin film 312. As a result, a small gap 317 exists between the resin film 312 and the covering material 323, and the region where the laminate 311 is contained in the resin film 312 communicates with the external region of the heat-transfer-suppressing sheet 140 via the first hole 314, the gap 317, and the second hole 315. Therefore, when the heat-transfer-suppressing sheet 140 is heated to a high temperature due to an increase in the temperature of the battery cells 20a, 20b, and 20c, the gas in the internal region contained in the resin film 312 can be discharged to the outside.

[0142] In the third and fourth embodiments, the laminate 311 may be one in which the elastic sheet 51 is laminated on at least one of the first surface 10a and the second surface 10b of the heat insulating material 10. Specifically, the elastic sheet 51 may be laminated only on the first surface 10a of the heat insulating material 10, or the elastic sheet 51 may be laminated on the first surface 10a and the second surface 10b of the heat insulating material 10. The elastic sheet 51 may be sandwiched between a pair of heat insulating materials 10, or the heat insulating material 10 may be sandwiched between a pair of elastic sheets 51. Furthermore, various sheets other than the heat insulating material 10 and the elastic sheet 51 may be laminated. For the heat insulating material 10, any of the heat insulating materials 10, 40, 60, 70, 80, 90, and 110 of the above-mentioned structural examples 1 to 7 may be used, and the effects specific to each heat insulating material can be obtained.

[0143] <Resin film> In the third and fourth embodiments, the material constituting the resin film 112, 312 can be at least one resin selected from polyethylene, polypropylene, polystyrene, vinyl chloride, nylon, acrylic, epoxy resin, polyurethane, polyether ether ketone, polyetherimide, polyethylene terephthalate, polyphenyl sulfide, polycarbonate, and aramid.

[0144] As shown in the second to fourth embodiments, it is preferable to use shrink packaging when covering the entire surface of the laminate 111, 311 with the resin film 112, 312. Therefore, it is more preferable to use the resin film 112, 312 made of a material suitable for shrink packaging. Such materials include polyethylene, polypropylene, polystyrene, polyethylene terephthalate, and polyvinyl chloride.

[0145] (Thickness of resin film) The resin film preferably has an appropriate thickness since it adheres to the outer surface of the laminate, prevents particles from falling off, and prevents the heat insulating material and the elastic sheet 51 from slipping out of place. Furthermore, the resin film preferably has appropriate flexibility so that the resin film is at least partially adhered to the shape of the laminate. If the thickness of the resin film exceeds 1 mm, it becomes difficult to make the resin film conform to the shape of the laminate 111, 311, and there is a risk of cracks or breaks occurring in the resin film. Therefore, the thickness of the resin film is preferably 1 mm or less, more preferably 0.1 mm or less, and even more preferably 0.05 mm or less. On the other hand, there is no particular lower limit to the thickness of the resin film, but in order to prevent tearing due to friction with battery cells, etc., and to obtain the desired strength, the thickness is preferably 0.005 mm or more, and more preferably 0.01 mm or more.

[0146] (Other materials contained in the resin film) In addition, since the resin film is required to be resistant to the high temperatures of the battery cells 20a, 20b, and 20c, it is preferable that the resin film has flame retardancy, and specifically, it is preferable that the resin film contains an inorganic substance or a flame retardant. Other materials contained in the resin film include inorganic substances such as talc, calcium carbonate, aluminum hydroxide, titanium oxide, vermiculite, zeolite, synthetic silica, zirconia, zircon, barium titanate, zinc oxide, and alumina, and flame retardants such as bromine-based flame retardants, chlorine-based flame retardants, phosphorus-based flame retardants, boron-based flame retardants, silicone-based flame retardants, and nitrogen-containing compounds.

[0147] <Coating material> In the third and fourth embodiments, the materials constituting the covering materials 313 and 323 may be the same as those of the resin film 312, but the covering materials 313 and 323 may be made of the same material as the resin film 312 or may be made of a different material. When the covering material 323 is attached to the surface of the resin film 312 by shrink packaging as shown in Figures 24A and 24B, it is preferable that the covering material 323 contains a material suitable for the shrink packaging.

[0148] [Fifth embodiment] FIG. 25A is a top view showing a heat-transfer-suppressing sheet according to a fifth embodiment of the present invention, and FIG. 25B is a cross-sectional view in the thickness direction thereof. The heat transfer-suppressing sheet 150 according to the fifth embodiment includes a laminate 511 and an expansion-suppressing sheet 512. The laminate 511 is formed by stacking the heat insulating material 10 and the elastic sheet 51 shown in the first to fourth embodiments. In FIG. 25A, the heat insulating material 10 and the elastic sheet 51 are not shown, and only the laminate 511 is shown. The laminate 511 has a pair of main surfaces 511a perpendicular to the thickness direction and an end surface 511b approximately parallel to the thickness direction. In the fifth embodiment, the expansion-suppressing sheet 512 is formed continuously along the end surface 511b of the laminate 511 so as to cover the end surface 511b. As will be described later, the expansion-suppressing sheet 512 has specific physical properties and has the effect of suppressing the end surface 511b of the laminate 511 from expanding outward.

[0149] A specific example of application of the heat-transfer-reducing sheet 150 configured as described above to a battery pack will be described below. Here, the case where the heat-transfer-reducing sheet 150 shown in Fig. 25A and Fig. 25B is applied instead of the heat-transfer-reducing sheet 50 of the battery pack 100 shown in Fig. 2 will be described.

[0150] In the battery pack 100, when the temperature of at least one of the battery cells 20a, 20b, and 20c rises, the heat transfer suppression sheet 150 having a heat insulating material with excellent heat insulating properties is interposed between the adjacent battery cells, so that the heat transfer between the battery cells can be suppressed. In addition, in the battery pack 100, when the battery cells 20a, 20b, and 20c expand due to charging and discharging, etc., a pressing force F1 is applied toward the main surface 511a of the laminate 511, as shown in FIG. 25B. Since the laminate 511 has an elastic sheet, the main surface 511a is pressed and the thickness of the elastic sheet is reduced, and a part of the volume of the elastic sheet tries to escape to an area that is not pressed, generating an expansion force F2. In the fifth embodiment, the expansion suppression sheet 512 covers the end surface 511b of the laminate 511, and the expansion suppression sheet 512 presses the end surface 511b of the laminate 511 inward with a pressing force F3, so that the end surface of the elastic sheet can be suppressed from expanding outward.

[0151] As a result, it is possible to prevent misalignment or rattling between the battery cells 20a, 20b, and 20c and the heat-transfer-suppressing sheet 150, and to prevent a decrease in performance of the battery pack. Even if the main surface 511a of the laminate 511 is pressed with a high pressing force F1, it is possible to prevent the elastic sheets constituting the laminate 511 from being significantly compressed and deformed, and thus to prevent an excessive reduction in thickness, and it is possible to maintain the thermal insulation between the battery cells 20a, 20b, and 20c.

[0152] Although it is possible to suppress bulging of the end faces of the elastic sheet by appropriately selecting the material of the elastic sheet and controlling the elastic modulus, according to this embodiment, regardless of the material of the elastic sheet, bulging can be suppressed simply by attaching the bulge suppression sheet 512. This increases the latitude in selecting the elastic sheet, allowing the free selection of an elastic sheet having desired properties other than the elastic modulus.

[0153] The bulge-suppressing sheet 512 may or may not be in close contact with the end surface 511b of the laminate 511, but if it is in close contact, it can prevent the bulge-suppressing sheet 512 from coming off the laminate 511. The bulge-suppressing sheet 512 only needs to be present on at least the end surface of the elastic sheet, but it is preferably disposed so as to cover the end surface 511b of the laminate 511.

[0154] [Sixth embodiment] Fig. 26A is a cross-sectional view in the thickness direction showing a heat-transfer-suppressing sheet according to a sixth embodiment of the present invention, and Fig. 26B is a top view seen from the main surface side. In the sixth embodiment shown in Fig. 26A and Fig. 26B, the same components as those in the fifth embodiment shown in Fig. 25A and Fig. 25B are given the same reference numerals, and detailed descriptions thereof will be omitted or simplified.

[0155] 26A, in a heat-transfer-suppressing sheet 160 according to the sixth embodiment, a pair of elastic sheets 51 are laminated on a pair of main surfaces 510a of a thermal insulator 10 to form a laminate 511. The bulge-suppressing sheet 514 encases the laminate 511. Thus, the bulge-suppressing sheet 514 is composed of outer main surface side portions 514a covering the pair of main surfaces 511a of the laminate 511 and outer end surface side portions 514b covering the end surfaces 511b of the laminate 511, and the outer main surface side portions 514a and the outer end surface side portions 514b are formed continuously.

[0156] In the sixth embodiment configured in this manner, since the heat insulating material 10 having excellent heat insulating properties is disposed, the transfer of heat between the battery cells can be suppressed. In addition, the outer end surface side portion 514b of the bulge-suppressing sheet 514 is disposed on the end surface 511b side of the laminate 511, and the outer end surface side portion 514b presses the end surface of the elastic sheet 51 inward. Therefore, the end surface of the elastic sheet 51 can be suppressed from bulging outward. As a result, when the heat-transfer-suppressing sheet 160 according to the sixth embodiment is applied to the battery pack 100, it is possible to prevent a decrease in the performance of the battery pack caused by misalignment or rattling between the battery cells 20a, 20b, and 20c and the heat-transfer-suppressing sheet 160. In addition, it is possible to suppress a decrease in the heat insulating properties caused by a decrease in the thickness of the elastic sheet 51.

[0157] Furthermore, in the sixth embodiment, the bulge-control sheet 514 encloses the entire laminate 511, and therefore, it is possible to prevent inorganic particles and the like contained in the heat insulating material from falling off.

[0158] The main surface 511a of the laminate 511 and the outer main surface side portion 514a of the swell-suppressing sheet 514 may or may not be in contact with each other, and another functional member may be interposed between the main surface 511a of the laminate 511 and the outer main surface side portion 514a of the swell-suppressing sheet 514. Similarly, the end surface 511b of the laminate 511 and the outer end surface side portion 514b of the swell-suppressing sheet 514 may or may not be in direct contact with each other. Specifically, it is sufficient that the effect of suppressing the swell of the end surface of the elastic sheet 51 can be obtained by disposing the swell-suppressing sheet 514, and another functional sheet may be interposed between the end surface of the elastic sheet 51 and the outer end surface side portion 514b of the swell-suppressing sheet 514.

[0159] 26A, the elastic sheets 51 are disposed on both main surfaces of the thermal insulation material 10, but for example, the elastic sheets 51 may be disposed on only one main surface 11a of the thermal insulation material 10. Also, the thermal insulation material 10 may be disposed on both main surfaces of the elastic sheet 51.

[0160] Furthermore, as shown in FIG. 26B, it is preferable that outer end surface side portion 514b of expansion-suppressing sheet 514 of heat-transfer-suppressing sheet 160 has linear thick portion 516 extending in a direction approximately parallel to main surface 511a of laminate 511.

[0161] If the thick portion 516 is provided on the outer end surface side portion 514b of the bulge-suppressing sheet 514, the effect of suppressing outward bulging of the end surface of the elastic sheet 51 can be further improved. It is preferable that at least a part of the thick portion 516 is curved or meandering. If a meandering region is present in the thick portion 516, when the end surface of the elastic sheet 51 bulges, the outer end surface side portion 514b stretches slightly in response to the bulge, and the meandering thick portion 516 also stretches accordingly. Thereafter, when the pressure applied to the heat transfer-suppressing sheet 160 by the battery cells 20a, 20b, and 20c decreases and the elastic sheet 51 contracts, the end surface of the elastic sheet 51 retreats inward. At this time, the thick portion 516 attempts to return to its serpentine shape, and a force is generated on the outer end surface side portion 514b of the bulge-suppressing sheet 514 that follows the retreat of the end surface of the elastic sheet 51, so that the bulge-suppressing effect of the bulge-suppressing sheet 514 can be maintained for a long period of time.

[0162] Although the thick portion 516 is effective in suppressing bulging if it is formed so as to go around the outer end surface side portion 514b of the bulge-suppressing sheet 514, it is not necessary to form it so as to go around, and the above effect can be obtained as long as it is formed in at least a partial area of ​​the outer end surface side portion 514b. Similarly, it is not necessary for the thick portion 516 to be curved or meandering over the entire area, and the above effect can be obtained as long as at least a part of the thick portion is curved or meandering.

[0163] In the fifth and sixth embodiments, the laminate 511 may be one in which the elastic sheet 51 is laminated on at least one of the first surface 10a and the second surface 10b of the heat insulating material 10. Specifically, the elastic sheet 51 may be laminated only on the first surface 10a of the heat insulating material 10, or the elastic sheet 51 may be laminated on the first surface 10a and the second surface 10b of the heat insulating material 10. The elastic sheet 51 may be sandwiched between a pair of heat insulating materials 10, or the heat insulating material 10 may be sandwiched between a pair of elastic sheets 51. Furthermore, various sheets other than the heat insulating material 10 and the elastic sheet 51 may be laminated. For the heat insulating material 10, any of the heat insulating materials 10, 40, 60, 70, 80, 90, and 110 of the above-mentioned structural examples 1 to 7 may be used, and the effects specific to each heat insulating material can be obtained.

[0164] <Bulge suppression sheet> The material constituting the expansion suppression sheet can be at least one resin selected from polyethylene, polypropylene, polystyrene, vinyl chloride, nylon, acrylic, epoxy resin, polyurethane, polyether ether ketone, polyetherimide, polyethylene terephthalate, polyphenyl sulfide, polycarbonate and aramid.

[0165] 25A to 26B, it is preferable to use shrink packaging when covering the entire surface of laminate 511 with expansion-control sheets 512 and 514. Therefore, it is more preferable to use an expansion-control sheet made of a material suitable for shrink packaging. Examples of such materials include polyethylene, polypropylene, polystyrene, polyethylene terephthalate, and polyvinyl chloride.

[0166] (Characteristics of the expansion suppression sheet) In this embodiment, the bulge-suppressing sheet preferably has an appropriate tensile strength in order to have the effect of preventing bulging at the end surface 511b by being in close contact with the end surface 511b of the laminate 511 (especially the elastic sheet 51). Furthermore, in order for the bulge-suppressing sheet to fully obtain the effect of suppressing bulging along the end surface of the elastic sheet 51, it is also preferable for the bulge-suppressing sheet to have an appropriate tensile elongation.

[0167] (Tensile strength of expansion suppression sheet) If the tensile strength of the bulge-suppressing sheet is less than 20 MPa, when the end face of the elastic sheet 51 bulges outward, it will be destroyed immediately, and the bulge-suppressing effect will not be sufficiently obtained. Therefore, the tensile strength of the bulge-suppressing sheet is set to 20 MPa or more, preferably 30 MPa or more, and more preferably 40 MPa or more. On the other hand, if the tensile strength of the bulge-preventing sheet is 150 MPa or less, the effect of preventing bulging of the end faces of elastic sheet 51 can be appropriately controlled, and the effect of absorbing deformation of battery cells 20a, 20b, 20c by elastic sheet 51 can be sufficiently obtained. Therefore, the tensile strength of the bulge-preventing sheet is preferably 150 MPa or less, more preferably 130 MPa or less, and even more preferably 100 MPa or less.

[0168] (Thickness of expansion suppression sheet) If the thickness of the bulge-controlling sheet exceeds 1 mm, it becomes difficult for the sheet to conform to the shape of the laminate 511, and cracks or breaks may occur. Therefore, the thickness of the bulge-controlling sheet is preferably 1 mm or less, more preferably 0.1 mm or less, and even more preferably 0.05 mm or less. On the other hand, there is no particular lower limit to the thickness of the swell-control sheet, but in order to obtain the desired tensile strength, it is preferably 0.005 mm or more, and more preferably 0.01 mm or more.

[0169] <Other materials included in the swelling control sheet> In addition, since the bulge-suppressing sheet contacts the battery cells 20a, 20b, and 20c, it is preferable that the sheet has flame retardancy, and specifically, it is preferable that the sheet contains an inorganic substance or a flame retardant. Examples of the materials constituting the bulge-suppressing sheet include inorganic substances such as talc, calcium carbonate, aluminum hydroxide, titanium oxide, vermiculite, zeolite, synthetic silica, zirconia, zircon, barium titanate, zinc oxide, and alumina, and examples of the flame retardant include bromine-based flame retardants, chlorine-based flame retardants, phosphorus-based flame retardants, boron-based flame retardants, silicone-based flame retardants, and nitrogen-containing compounds.

[0170] [Seventh embodiment] 27 is a perspective view showing a heat-transfer-suppressing sheet according to a seventh embodiment of the present invention. A heat-transfer-suppressing sheet 170 according to the seventh embodiment has an elastic sheet 751 laminated on one main surface of a thermal insulation material 10, and the elastic sheet 751 is formed to be smaller than the thermal insulation material 10 in a plan view. The elastic sheet 751 is made of an elastic body that maintains a compressed state when the temperature is less than 90° C. and is released from the compressed state and expands when the temperature reaches 90° C. or higher. A known elastic body can be used as the elastic body itself, and the elastic material that constitutes the elastic body will be described in detail later.

[0171] In order to maintain the elastic sheet 751 in a compressed state, in this embodiment, a binder substance is mixed with an elastic material and processed into a sheet shape to form the elastic sheet 751. Considering that the binder substance is melted at 90°C or higher to release the compressed state of the elastic body, an organic binder is preferable. Examples of organic binders include acrylic, methacrylic, styrene, and butadiene resins. The amount of binder substance to be mixed can be appropriately selected depending on the type of binder substance, the degree of compression of the elastic body, and the elastic ability of the elastic body, but it is appropriate that the binder substance is contained in an amount of 5 to 30 mass% with respect to the total mass of the elastic sheet 751.

[0172] The elastic sheet 751 and the heat insulating material 10 may be bonded together over the entire surface, or may be bonded partially in spots. When the elastic sheet 751 and the heat insulating material 10 are bonded together, the heat transfer-suppressing sheet 170 is easier to handle. When the elastic sheet 751 is released from the compressed state, the elastic sheet 751 expands in the thickness direction and the surface direction, so it is preferable that the elastic sheet 751 is partially bonded to the heat insulating material 10 so as not to hinder the expansion in the surface direction. In this case, it is preferable that the center portion of the elastic sheet 751 and the heat insulating material 10 are bonded together.

[0173] 27, elastic sheet 751 is shaped to be smaller than thermal insulation material 10 in consideration of expansion in the planar direction, but elastic sheet 751 and thermal insulation material 10 may be the same size. If elastic sheet 751 and thermal insulation material 10 are shaped to be the same size, when elastic sheet 751 expands, elastic sheet 751 also spreads into the space around thermal insulation material 10, and when applied to a battery pack, for example, it is expected that battery cells adjacent to a battery cell that has experienced thermal runaway will be protected.

[0174] FIG. 28 is a perspective view of a modified heat-transfer-suppressing sheet according to the seventh embodiment of the present invention, showing the state below 90° C. FIG. 29 is a cross-sectional view of a modified heat-transfer-suppressing sheet according to the seventh embodiment of the present invention, showing the state above 90° C. As shown in FIG. 28, in the heat-transfer-suppressing sheet 180, the elastic sheet 751 may be composed of a plurality of divided elastic sheets 751A. The divided elastic sheets 751A are arranged at substantially equal intervals on the surface of the heat insulating material 10, and gaps 702 are formed between adjacent divided elastic sheets 751A. When the divided elastic sheets 751A are in a compressed state, that is, below 90° C., the gaps 702 become air passages and provide a cooling effect, so that the heat insulating performance of the heat-transfer-suppressing sheet 180 can be improved.

[0175] On the other hand, at temperatures above 90°C, each divided elastic sheet 751A expands and closes gaps 702, improving the elastic performance. Furthermore, when divided elastic sheets 751A expand further, the end faces of adjacent divided elastic sheets 751A come into contact with each other, forming mountain-shaped gaps 702A, as shown in Fig. 29. These mountain-shaped gaps 702A act as air passages and provide a cooling effect, so that the heat insulating performance of heat-transfer-suppressing sheet 180 can be improved even in a temperature range of 90°C or higher.

[0176] 27 to 29, the heat-transfer-suppressing sheets 170, 180 may be formed by laminating a compressed elastic sheet 751, a divided elastic sheet 751A, and a thermal insulator 10. Furthermore, as shown in the following eighth embodiment, the compressed elastic sheet 751 and the divided elastic sheet 751A may be formed by a heat-compressible packaging body.

[0177] [Eighth embodiment] FIG. 30 is a schematic cross-sectional view showing a heat transfer-suppressing sheet according to an eighth embodiment of the present invention. As shown in FIG. 30, the heat transfer-suppressing sheet 190 according to the eighth embodiment has a laminate in which an elastic sheet 751 is laminated on one main surface of a heat insulating material 10, and this laminate is surrounded by a heat-shrinkable wrapping body 715. The wrapping body 715 is shrunk by heat, thereby maintaining the compressed state of the elastic sheet 751. In FIG. 30, the wrapping body 715 is shown by a thick solid line, and in this embodiment, the entire laminate of the heat insulating material 10 and the elastic sheet 751 is surrounded with almost no gaps. Note that even in a state in which the heat insulating material 10 is surrounded and shrunk by the wrapping body 715, there is almost no change in shape, but the elastic sheet 751 has an area slightly smaller than that of the heat insulating material 10 due to the shrinkage of the wrapping body 715.

[0178] The elastic sheet 751 may be formed of a plurality of divided elastic sheets 751A, as in the seventh embodiment, and the elastic sheet 751 and the heat insulating material 10 may be bonded to each other partially or entirely.

[0179] A sheet or film made of a heat-shrinkable resin can be used for the wrapping body 715, and may be either non-perforated or perforated. If perforated, wrapping body 715 breaks at the perforations at 90° C. or higher, making elastic sheet 751 more likely to expand.

[0180] In the seventh embodiment and its modified example, and the eighth embodiment, the elastic sheet 751 and the divided elastic sheet 751A may be laminated on only one main surface of the heat insulating material 10, or on both main surfaces. The elastic sheet 751 and the divided elastic sheet 751A may be sandwiched between a pair of heat insulating materials 10. However, in a configuration in which the divided elastic sheet 751A is sandwiched between a pair of heat insulating materials 10, even if the divided elastic sheet 751A further expands, the gap 702A is unlikely to be formed. Furthermore, various sheets other than the heat insulating material 10, the elastic sheet 751, and the divided elastic sheet 751A may be laminated. For the heat insulating material 10, any of the heat insulating materials 10, 40, 60, 70, 80, 90, and 110 of the above-mentioned structural examples 1 to 7 can be used, and the effects specific to each heat insulating material can be obtained.

[0181] Examples of heat-shrinkable resins constituting the packaging body 715 include polyethylene, polypropylene, polystyrene, polyethylene terephthalate, and vinyl chloride. There is no limit to the thickness of the packaging body 715 as long as the compressed state of the elastic sheet 751 can be maintained, but if the thickness of the packaging body 715 exceeds 1 mm, it becomes difficult to make the packaging body 715 conform to the shape of the insulating material, and there is a risk of cracks or breakage. Therefore, it is preferably 1 mm or less, more preferably 0.1 mm or less, and even more preferably 0.05 mm or less. On the other hand, the lower limit is preferably 0.005 mm or more, and more preferably 0.01 mm or more, in order to prevent tearing due to friction with the battery cells when applied to, for example, an assembled battery.

[0182] The materials constituting the heat-transfer-suppressing sheet according to this embodiment will be described below. First, the materials constituting the heat insulating material will be described.

[0183] <Organic fiber> The organic fiber 1 gives flexibility to the heat insulating material, and has the effect of maintaining the strength and shape of the sheet by welding the inorganic particles 4 and other organic fibers 1 to the surface of the organic fiber 1. Although a single-component organic fiber can be used as the material of the organic fiber 1 in the heat insulating material, it is preferable to use a binder fiber with a core-sheath structure. The binder fiber with a core-sheath structure has a core extending in the longitudinal direction of the fiber and a sheath formed to cover the outer peripheral surface of the core. In addition, the core is made of a first organic material, the sheath is made of a second organic material, and the melting point of the first organic material is higher than the melting point of the second organic material. When the binder fiber with a core-sheath structure is used as a material, the core corresponds to the organic fiber 1 in the heat insulating material. In addition, during the production of the heat insulating material, the second organic material constituting the sheath melts and then solidifies again, so that the sheath becomes the welded part 5 in the heat insulating material.

[0184] When a binder fiber having a core-sheath structure is used as the material of the organic fiber 1, the core, i.e., the first organic material constituting the organic fiber 1, is not particularly limited as long as it has a melting point higher than that of the sheath, i.e., the second organic material present on the outer peripheral surface of the organic fiber 1. The first organic material may be at least one selected from polyethylene terephthalate, polypropylene, and nylon.

[0185] (Organic fiber content) In this embodiment, if the content of the organic fiber 1 in the heat insulating material is appropriately controlled, the effect of reinforcing the skeleton can be sufficiently obtained. The content of the organic fibers 1 is preferably 5% by mass or more, and more preferably 10% by mass or more, based on the total mass of the heat insulating material. If the content of the organic fibers 1 is too high, the content of the inorganic particles 4 will relatively decrease, so in order to obtain the desired heat insulating performance, the content of the organic fibers is preferably 25% by mass or less, and more preferably 20% by mass or less, based on the total mass of the heat insulating material.

[0186] (Organic fiber length) The fiber length of the organic fibers 1 is not particularly limited, but from the viewpoint of ensuring moldability and processability, it is preferable that the average fiber length of the organic fibers is 10 mm or less. On the other hand, from the viewpoint of making the organic fibers 1 function as a skeleton and ensuring the compressive strength of the heat insulating material, it is preferable that the average fiber length of the organic fibers 1 is 0.5 mm or more.

[0187] <Welded part> The welded portion 5 is formed by heating and melting the surface of the organic fiber 1 or the sheath of the binder fiber having a core-sheath structure, and then cooling it, and serves to weld the inorganic particles 4 to the surface of the organic fiber 1 and also to weld the organic fibers 1 together. When a binder fiber having a core-sheath structure is used as the material for the organic fiber 1, the welded portion 5 contains the second organic material that constitutes the sheath.

[0188] (Second organic material) The second organic material is not particularly limited as long as it has a melting point lower than that of the first organic material constituting the organic fiber 1. The second organic material may be at least one selected from the group consisting of polyethylene terephthalate, polyethylene, polypropylene, and nylon. The melting point of the second organic material is preferably 90° C. or higher, and more preferably 100° C. or higher. The melting point of the second organic material is preferably 150° C. or lower, and more preferably 130° C. or lower.

[0189] <Inorganic particles> As the inorganic particles, a single inorganic particle may be used, or two or more types of inorganic particles may be used in combination. As the type of inorganic particles, from the viewpoint of the heat transfer suppression effect, it is preferable to use particles made of at least one inorganic material selected from oxide particles, carbide particles, nitride particles, and inorganic hydrate particles, and it is more preferable to use oxide particles. In addition, the shape is not particularly limited, but it is preferable to include at least one selected from nanoparticles, hollow particles, and porous particles, and specifically, silica nanoparticles, metal oxide particles, inorganic balloons such as microporous particles and hollow silica particles, particles made of thermally expandable inorganic materials, particles made of water-containing porous bodies, etc. can also be used.

[0190] If the average secondary particle diameter of the inorganic particles is 0.01 μm or more, they are easily available and the increase in production costs can be suppressed. If the average secondary particle diameter is 200 μm or less, the desired heat insulating effect can be obtained. Therefore, the average secondary particle diameter of the inorganic particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.

[0191] In addition, when two or more kinds of inorganic particles having different heat transfer suppression effects are used in combination, the heating body can be cooled in multiple stages, and the heat absorption effect can be expressed in a wider temperature range. Specifically, it is preferable to use a mixture of large-diameter particles and small-diameter particles. For example, when nanoparticles are used as one inorganic particle, it is preferable to include inorganic particles made of metal oxide as the other inorganic particle. Hereinafter, the inorganic particles will be described in more detail, with the small-diameter inorganic particles being referred to as the first inorganic particles and the large-diameter inorganic particles being referred to as the second inorganic particles.

[0192] <First inorganic particle> (Oxide particles) Since oxide particles have a high refractive index and a strong effect of scattering light, when oxide particles are used as the first inorganic particles, radiation heat transfer can be suppressed, particularly in high temperature regions such as abnormal heat generation. As the oxide particles, at least one type of particle selected from silica, titania, zirconia, zircon, barium titanate, zinc oxide, and alumina can be used. That is, among the above oxide particles that can be used as inorganic particles, only one type may be used, or two or more types of oxide particles may be used. In particular, silica is a component with high heat insulation properties, and titania is a component with a high refractive index compared to other metal oxides, and has a high effect of scattering light and blocking radiant heat in high temperature regions of 500°C or more, so it is most preferable to use silica and titania as the oxide particles.

[0193] (Average primary particle size of oxide particles: 0.001 μm to 50 μm) The particle size of the oxide particles can affect the effect of reflecting radiant heat, so if the average primary particle size is limited to a predetermined range, even higher heat insulation can be obtained. In other words, when the average primary particle diameter of the oxide particles is 0.001 μm or more, it is sufficiently larger than the wavelength of light that contributes to heating and efficiently diffuses the light, thereby suppressing the radiation heat transfer within the insulation material in the high temperature range of 500°C or more, thereby further improving the insulation properties. On the other hand, if the average primary particle size of the oxide particles is 50 μm or less, the number and number of contact points between the particles do not increase even when compressed, making it difficult to form a conductive heat transfer path, thereby reducing the impact on insulation, especially in the normal temperature range where conductive heat transfer is dominant.

[0194] In the present invention, the average primary particle size can be determined by observing particles under a microscope, comparing with a standard scale, and taking the average of any ten particles.

[0195] (Nanoparticles) In the present invention, nanoparticles refer to particles of the order of nanometers that are spherical or nearly spherical and have an average primary particle diameter of less than 1 μm. Nanoparticles have a low density and therefore suppress conductive heat transfer. When nanoparticles are used as the first inorganic particles, the three-dimensionally connected pores 7 are further refined, and excellent heat insulation properties that suppress convective heat transfer can be obtained. For this reason, it is preferable to use nanoparticles in that heat transfer between adjacent nanoparticles can be suppressed when the battery is used in the normal room temperature range. Furthermore, if nanoparticles with a small average primary particle size are used as the oxide particles, the increase in conductive heat transfer of the insulating material can be suppressed even if the insulating material is compressed due to expansion caused by thermal runaway of the battery cell and the internal density increases. This is thought to be because nanoparticles are prone to forming fine gaps between particles due to electrostatic repulsion, and because they have a low bulk density, the particles are packed together to provide cushioning properties.

[0196] In the present invention, when nanoparticles are used as the first inorganic particles, there is no particular limitation on the material as long as it meets the above definition of nanoparticles. For example, silica nanoparticles are a material with high heat insulation properties, and since the contact points between particles are small, the amount of heat conducted by silica nanoparticles is smaller than that when silica particles with a large particle size are used. Furthermore, silica nanoparticles that are generally available have a bulk density of 0.1 (g / cm 3 ), for example, even if the battery cells arranged on both sides of the insulating material thermally expand and a large compressive stress is applied to the insulating material, the size (area) and number of contacts between the silica nanoparticles do not increase significantly, and the insulating properties can be maintained. Therefore, it is preferable to use silica nanoparticles as the nanoparticles. Examples of silica nanoparticles include wet silica, dry silica, and aerogel, but silica nanoparticles that are particularly suitable for this embodiment will be described below.

[0197] Generally, wet silica particles are aggregated, whereas dry silica particles can be dispersed. In the temperature range below 300℃, heat conduction is dominated by conductive heat transfer, so dry silica particles can be dispersed, which provides better heat insulation performance than wet silica. In addition, the heat insulating material according to the present embodiment is preferably produced by a manufacturing method in which a mixture containing the material is processed into a sheet shape by a dry method. Therefore, it is preferable to use dry silica, silica aerogel, or the like, which has low thermal conductivity, as the inorganic particles.

[0198] (Average primary particle size of nanoparticles: 1 nm to 100 nm) By limiting the average primary particle size of the nanoparticles to a predetermined range, even higher heat insulation properties can be obtained. That is, when the average primary particle size of the nanoparticles is 1 nm or more and 100 nm or less, it is possible to suppress convective heat transfer and conductive heat transfer within the insulating material, particularly in the temperature range below 500° C., and to further improve the insulating properties. Even when compressive stress is applied, the gaps remaining between the nanoparticles and the contact points between many particles suppress conductive heat transfer, and the insulating properties of the insulating material can be maintained. The average primary particle size of the nanoparticles is more preferably 2 nm or more, and even more preferably 3 nm or more, while the average primary particle size of the nanoparticles is more preferably 50 nm or less, and even more preferably 10 nm or less.

[0199] (Inorganic hydrate particles) When inorganic hydrate particles receive heat from a heating element and reach a temperature above the thermal decomposition initiation temperature, they undergo thermal decomposition and release their own water of crystallization to lower the temperature of the heating element and its surroundings, thus exerting the so-called "endothermic effect". After releasing the water of crystallization, the particles become porous and exert a heat insulating effect due to the countless air holes. A specific example of an inorganic hydrate is aluminum hydroxide (Al(OH) 3 ), magnesium hydroxide (Mg(OH) 2 ), calcium hydroxide (Ca(OH) 2 ), zinc hydroxide (Zn(OH)2 ), iron hydroxide (Fe(OH) 2 ), manganese hydroxide (Mn(OH) 2 ), zirconium hydroxide (Zr(OH) 2 ), gallium hydroxide (Ga(OH) 3 ) etc.

[0200] For example, aluminum hydroxide contains about 35% water of crystallization, and as shown in the following formula, it decomposes thermally and releases the water of crystallization, thereby exerting an endothermic effect. After releasing the water of crystallization, it becomes a porous alumina (Al 2 O 3 ) and acts as a thermal insulator. 2Al(OH) 3 →Al 2 O 3 +3H 2 O

[0201] Heat transfer-suppressing sheet 50 according to this embodiment is preferably interposed between battery cells, for example, but in a battery cell that has experienced thermal runaway, the temperature rises rapidly to over 200° C. and continues to rise to around 700° C. Therefore, it is preferable that the inorganic particles be made of inorganic hydrates whose thermal decomposition starting temperature is 200° C. or higher. The thermal decomposition onset temperatures of the inorganic hydrates listed above are approximately 200°C for aluminum hydroxide, approximately 330°C for magnesium hydroxide, approximately 580°C for calcium hydroxide, approximately 200°C for zinc hydroxide, approximately 350°C for iron hydroxide, approximately 300°C for manganese hydroxide, approximately 300°C for zirconium hydroxide, and approximately 300°C for gallium hydroxide. All of these temperatures roughly overlap with the temperature range of the sudden temperature rise in a battery cell that has experienced thermal runaway, and can efficiently suppress the temperature rise, making these inorganic hydrates preferable.

[0202] (Average secondary particle diameter of inorganic hydrate particles: 0.01 μm or more and 200 μm or less) In addition, when inorganic hydrate particles are used as the first inorganic particles, if the average particle size is too large, the first inorganic particles (inorganic hydrate) near the center of the heat insulating material require a certain amount of time to reach their thermal decomposition temperature, and the first inorganic particles near the center of the sheet may not be completely thermally decomposed. For this reason, the average secondary particle size of the inorganic hydrate particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.

[0203] (Particles made of thermally expandable inorganic material) Examples of the thermally expandable inorganic material include vermiculite, bentonite, mica, and perlite.

[0204] (Particles made of water-containing porous material) Specific examples of the hydrous porous body include zeolite, kaolinite, montmorillonite, acid clay, diatomaceous earth, wet silica, dry silica, aerogel, mica, and vermiculite.

[0205] (Inorganic balloon) The heat insulating material used in the present invention may contain inorganic balloons as the first inorganic particles. When inorganic balloons are contained, convective or conductive heat transfer within the insulating material can be suppressed in the temperature range below 500° C., and the insulating properties of the insulating material can be further improved. As the inorganic balloons, at least one selected from the group consisting of shirasu balloons, silica balloons, fly ash balloons, barite balloons, and glass balloons can be used.

[0206] (Inorganic balloon content: 60% or less by mass of the total mass of the insulation material) The content of the inorganic balloons is preferably 60 mass % or less based on the total mass of the heat insulating material.

[0207] (Average particle size of inorganic balloons: 1 μm to 100 μm) The average particle size of the inorganic balloons is preferably 1 μm or more and 100 μm or less.

[0208] <Second inorganic particles> When two types of inorganic particles are contained in the heat insulating material, the second inorganic particles are not particularly limited as long as they are different from the first inorganic particles in terms of material, particle size, etc. As the second inorganic particles, oxide particles, carbide particles, nitride particles, inorganic hydrate particles, silica nanoparticles, metal oxide particles, inorganic balloons such as microporous particles and hollow silica particles, particles made of a thermally expandable inorganic material, particles made of a water-containing porous body, etc. can be used, and the details of these are as described above.

[0209] In addition, nanoparticles have extremely low conductive heat transfer and can maintain excellent heat insulation even when compressive stress is applied to the heat insulating material. Metal oxide particles such as titania have a high effect of blocking radiant heat. Furthermore, when large-diameter inorganic particles and small-diameter inorganic particles are used, the small-diameter inorganic particles enter the gaps between the large-diameter inorganic particles, resulting in a denser structure and improving the heat transfer suppression effect. Therefore, when nanoparticles are used as the first inorganic particles, for example, it is preferable to further include particles made of a metal oxide larger in diameter than the first inorganic particles as the second inorganic particles in the heat insulating material. Examples of metal oxides include silicon oxide, titanium oxide, aluminum oxide, barium titanate, zinc oxide, zircon, zirconium oxide, etc. In particular, titanium oxide (titania) is a component with a higher refractive index than other metal oxides, and is highly effective in scattering light and blocking radiant heat in a high temperature range of 500°C or higher, so it is most preferable to use titania.

[0210] When at least one type of particles selected from dry silica particles and silica aerogel is used as the first inorganic particles, and at least one type of particles selected from titania, zircon, zirconia, silicon carbide, zinc oxide and alumina is used as the second inorganic particles, in order to obtain excellent heat insulating performance within a temperature range of 300° C. or less, the first inorganic particles are preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more of the total mass of the inorganic particles. In addition, the first inorganic particles are preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 80% by mass or less of the total mass of the inorganic particles.

[0211] On the other hand, in order to obtain excellent heat insulating performance within a temperature range exceeding 300° C., the second inorganic particles are preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, based on the total mass of the inorganic particles. Also, the second inorganic particles are preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, based on the total mass of the inorganic particles.

[0212] (Average primary particle size of second inorganic particles) When second inorganic particles made of a metal oxide are contained in a heat insulating material, if the average primary particle size of the second inorganic particles is 1 μm or more and 50 μm or less, radiation heat transfer can be efficiently suppressed in a high temperature range of 500° C. or more. The average primary particle size of the second inorganic particles is more preferably 5 μm or more and 30 μm or less, and most preferably 10 μm or less.

[0213] (Inorganic particle content) In this embodiment, when the total content of the inorganic particles 4 in the heat insulating material is appropriately controlled, the heat insulating property of the heat insulating material can be sufficiently ensured. The total content of the inorganic particles 4 is preferably 60% by mass or more, and more preferably 70% by mass or more, based on the total mass of the heat insulating material. If the total content of the inorganic particles 4 is too high, the content of the organic fibers is relatively reduced, so that in order to sufficiently obtain the effect of reinforcing the skeleton and the effect of retaining the inorganic particles, the total content of the inorganic particles 4 is preferably 95% by mass or less, and more preferably 90% by mass or less, based on the total mass of the heat insulating material.

[0214] The content of the inorganic particles 4 in the heat insulating material can be calculated, for example, by heating the heat insulating material at 800° C., decomposing the organic matter, and then measuring the mass of the remaining part.

[0215] <Inorganic fibers> A single inorganic fiber may be used, or two or more types of inorganic fibers may be used in combination as the inorganic fiber 15. Examples of the inorganic fiber include ceramic fibers such as silica fiber, alumina fiber, alumina silicate fiber, zirconia fiber, carbon fiber, soluble fiber, refractory ceramic fiber, aerogel composite material, magnesium silicate fiber, alkaline earth silicate fiber, potassium titanate fiber, silicon carbide fiber, and potassium titanate whisker fiber, glass fibers such as glass fibers, glass wool, and slag wool, and natural mineral fibers other than these fibers, such as rock wool, basalt fiber, wollastonite, and mullite fiber. These inorganic fibers are preferred in terms of heat resistance, strength, availability, etc. Among the above inorganic fibers, the heat insulating material preferably contains at least one type selected from silica-alumina fiber, alumina fiber, silica fiber, rock wool, alkaline earth silicate fiber, and glass fiber, from the viewpoint of ease of handling.

[0216] The cross-sectional shape of the inorganic fiber is not particularly limited, and examples thereof include a circular cross section, a flat cross section, a hollow cross section, a polygonal cross section, a core cross section, etc. Among them, modified cross section fibers having a hollow cross section, a flat cross section, or a polygonal cross section are preferably used because they have slightly improved heat insulation properties.

[0217] The preferred lower limit of the average fiber length of the inorganic fibers is 0.1 mm, and the more preferred lower limit is 0.5 mm. On the other hand, the preferred upper limit of the average fiber length of the inorganic fibers is 50 mm, and the more preferred upper limit is 10 mm. If the average fiber length of the inorganic fibers is less than 0.1 mm, the inorganic fibers are less likely to be entangled with each other, and the mechanical strength of the insulating material may be reduced. On the other hand, if the average fiber length exceeds 50 mm, although a reinforcing effect is obtained, the inorganic fibers may not be able to be tightly entangled with each other, or may be curled up by a single inorganic fiber, which may lead to continuous voids, which may lead to a decrease in thermal insulation.

[0218] The preferred lower limit of the average fiber diameter of the inorganic fibers is 1 μm, more preferably 2 μm, and even more preferably 3 μm. On the other hand, the preferred upper limit of the average fiber diameter of the inorganic fibers is 15 μm, and more preferably 10 μm. If the average fiber diameter of the inorganic fibers is less than 1 μm, the mechanical strength of the inorganic fibers themselves may be reduced. In addition, from the viewpoint of the effect on human health, it is preferable that the average fiber diameter of the inorganic fibers is 3 μm or more. On the other hand, if the average fiber diameter of the inorganic fibers is more than 15 μm, the solid heat transfer through the inorganic fibers may increase, leading to a decrease in heat insulation, and the moldability and strength of the heat insulating material may be deteriorated.

[0219] (Inorganic fiber content) In this embodiment, when the heat insulating material contains inorganic fibers, the content of the inorganic fibers is preferably 3 mass % or more and 15 mass % or less with respect to the total mass of the heat insulating material.

[0220] The content of inorganic fibers is more preferably 5% by mass or more and 10% by mass or less based on the total mass of the heat insulating material. By setting the content at such a level, the shape retention, pressing force resistance, wind pressure resistance, and inorganic particle retention ability of the inorganic fibers are expressed in a well-balanced manner. In addition, by appropriately controlling the content of inorganic fibers, the organic fibers 1 and the inorganic fibers are entangled with each other to form a three-dimensional network, so that the effect of retaining the inorganic particles 4 and other compounding materials described later can be further improved.

[0221] <Other compounding materials> The heat insulating material according to the present embodiment may further contain a binder, a colorant, etc., as necessary. All of these are useful for the purpose of reinforcing the heat insulating material, improving its formability, etc., and the total amount of these is preferably 10 mass % or less based on the total mass of the heat insulating material.

[0222] <Elastic sheet> The elastic sheet is an elastic material processed into a sheet shape. Any known elastic material can be used. Specifically, a sheet made of rubber or thermoplastic elastomer that has elasticity that allows it to flexibly deform in response to deformation of the battery cells 20a, 20b, and 20c can be used.

[0223] The rubber may be either synthetic or natural rubber. Examples of synthetic rubber include styrene-butadiene rubber, butadiene rubber, chloroprene rubber, isoprene rubber, butyl rubber, ethylene propylene rubber, nitrile rubber, silicone rubber, fluororubber, acrylic rubber, urethane rubber, polysulfide rubber, epichlorohydrin rubber, and foamed silicone.

[0224] Examples of the thermoplastic elastomer include polystyrene-based, polyolefin-based, vinyl chloride-based, polyurethane-based, polyester-based, polyamide-based, and polybutadiene-based thermoplastic elastomers. The elastomer may be either porous or non-porous. If the elastomer is porous, the cell structure may be either closed cell type or open cell type.

[0225] (Elastic sheet size) The thickness of the elastic sheet is not particularly limited, but in order to effectively obtain the effect of the elastic sheet, it is preferable that the thickness be 1 mm or more and 10 mm or less.

[0226] [Thermal insulation] The heat insulating material used in the heat transfer suppressing sheet according to this embodiment is not particularly limited as long as it has a heat insulating effect. Thermal conductivity can be given as an index showing the heat insulating effect, and in this embodiment, the heat conductivity of the heat insulating material is preferably less than 1 (W / m·K), more preferably less than 0.5 (W / m·K), and even more preferably less than 0.2 (W / m·K). Furthermore, the heat conductivity of the heat insulating material is more preferably less than 0.1 (W / m·K), more preferably less than 0.05 (W / m·K), and particularly preferably less than 0.02 (W / m·K). The thermal conductivity of the insulating material can be measured in accordance with the "Test method for thermal conductivity of refractories" described in JIS R 2251.

[0227] In this embodiment, a composite insulation material in which the above insulation material and a mica sheet are laminated can also be used. The mica sheet is a mica sheet material containing mica processed into a sheet shape. Mica has excellent heat resistance and insulation properties, and a mica sheet made by processing a material containing mica into a sheet shape also has excellent impact resistance. Therefore, for example, when the battery cell 20a explodes due to high temperature and generates scattered debris, the composite insulation material can be prevented from being damaged. As a result, high insulation can be maintained between the battery cell 20a and the battery cell 20b.

[0228] The mica sheet material preferably contains oxide particles, oxide fibers, etc., in addition to mica. Specifically, SiO 2 , Al 2 O 3 , Ti 2 O 3 However, the present invention is not limited to these materials. It is more preferable to use a mica sheet made of natural minerals. The sheet shape may be a flat sheet without holes or may have holes. If holes are provided in at least a part of the center or other regions of the mica sheet, the mica sheet can follow the battery cells 20a, 20b, and 20c without cracking when the battery cells 20a, 20b, and 20c expand and contract.

[0229] (Insulation size) When laminating an insulating material and an elastic sheet, the size of the main surface of the insulating material and the size of the main surface perpendicular to the thickness direction of the elastic sheet may be approximately the same, or the elastic sheet may be formed smaller than the insulating material, as in the seventh and eighth embodiments shown in Figures 27 to 30. Here, "substantially the same" means that a difference in size between the two is acceptable up to ±5% of the average value of the two, preferably up to ±3%, and more preferably up to ±1%.

[0230] [Method of manufacturing heat transfer suppression sheet] The method for producing the heat-transfer-suppressing sheet according to this embodiment will be described in detail below, particularly with reference to an example in which the heat insulating material of Structural Example 2 is used. For example, binder fibers (not shown) having a core-sheath structure, inorganic particles 4, and inorganic fibers 15 are put into a mixer such as a V-type mixer in a predetermined ratio to prepare a mixture. As described above, it is preferable to use, as the binder fiber, fibers having a core-sheath structure with a core made of a first organic material and a sheath made of a second organic material, in which the melting point of the first organic material is higher than that of the second organic material.

[0231] The mixture is then placed in a mold and pressed with a press or the like, and the resulting molded body is heated to melt the sheath of the binder fiber. The heated molded body is then cooled, and the second organic material constituting the molten sheath and the inorganic particles 4 present around the binder fiber are fused to the core (organic fiber 1), and are also fused to each other in the regions where the binder fibers were in contact with each other. This allows the insulation material 40 to be processed into a sheet shape.

[0232] Thereafter, the elastic sheet 51 is placed on one of the main surfaces of the heat insulating material 40, and the two are fixed together. There are no particular limitations on the method for fixing the heat insulating material 40 and the elastic sheet 51 to each other, and various methods can be used, such as a method of adhering with an adhesive or the like, a method of sewing with thread or the like, a method of clamping and fixing with a fixing jig, a method of covering with a film or the like, a method of covering with a thermocompressive film and then heating to shrink the film and fix it, etc.

[0233] In addition, the insulating material 10 that does not contain inorganic fibers 15 and the insulating material that does not contain organic fibers 1 can be obtained in the same manufacturing method as the insulating material 40, and the use of the organic fibers 1 and the inorganic fibers 15 can be selected arbitrarily.

[0234] When the materials for the heat insulating material are mixed and pressurized and heated, the entangled organic fibers 1 exposed on the surface are heated and formed as a fiber layer 11 on the surface of the heat insulating material 40. The fiber layer 11 thus obtained has the effect of improving the strength of the heat insulating material 40 and mitigating impacts on the surface of the heat insulating material 40.

[0235] The above-mentioned heat insulating material is preferably manufactured by a dry method. When using a dry method, inorganic particles 4 suitable for the dry method are used, and a solvent such as water, which is necessary when forming by a wet method, is not added to the above mixture. However, in order to prevent powder such as inorganic particles 4 from flying around during the manufacture of the heat insulating material and making it difficult to handle the raw material, a small amount of solvent such as water can be added within the range of the dry method. For example, by adding a small amount of solvent such as water to the mixture, it is possible to suppress the scattering of inorganic particles during the manufacture.

[0236] In addition, the heat insulating material uses binder fibers with a core-sheath structure as a material, and since the melting point of the first organic material constituting the core is higher than that of the second organic material constituting the sheath, when the mixture is heated, the sheath can be melted while leaving the core. After cooling, the outer surface of the core (organic fiber 1) is covered with the second organic material containing inorganic particles 4, so that the inorganic particles 4 can be held. The organic fiber 1 to which the inorganic particles 4 are fused has an apparent thick fiber diameter, so that it has a higher strength than the organic fiber 1 alone. Furthermore, since the binder fibers are present in an irregular direction in the mixture, the organic fibers 1 are fused together in the region where the binder fibers are in contact with each other, forming a three-dimensional skeleton. As a result, the shape of the entire heat insulating material can be maintained with even higher strength.

[0237] Even if organic fibers without a core-sheath structure are used as binder fibers, it is possible to melt only the surface of the organic fibers while leaving the center of the organic fibers, and to coat the surface with inorganic particles or to fuse the organic fibers together, depending on the temperature setting. However, when manufacturing a heat insulating material, it is common to heat from one or both sides perpendicular to the thickness direction, and since a material with high heat insulating performance is used, strict temperature control is required to raise the temperature to the same level on the surface side and the center side in the thickness direction of the sheet.

[0238] In contrast, if binder fibers with a sheath-core structure in which the melting point of the first organic material constituting the core is higher than that of the second organic material constituting the sheath are used, it is very easy to set the temperature to leave the core and melt the sheath. As a result, the obtained heat insulating material has an ideal structure in which the organic fibers 1 are welded together on both the surface side and the center side to form a skeleton that maintains the strength of the sheet, and welded parts 5 containing inorganic particles 4 are formed on the surface of the organic fibers 1. Therefore, it is preferable to use binder fibers with the above-mentioned sheath-core structure as a material for the heat insulating material.

[0239] As described above, after laminating the heat insulating material and the elastic sheet 51, the surface of the laminate may be covered with a film or the like. Examples of the polymer film include films made of polyimide, polycarbonate, PET, p-phenylene sulfide, polyetherimide, crosslinked polyethylene, flame-retardant chloroprene rubber, polyvinyl denfluoride, rigid polyvinyl chloride, polybutylene terephthalate, PTFE, PFA, FEP, ETFE, rigid PCV, flame-retardant PET, polystyrene, polyethersulfone, polyamideimide, polyacrylonitrile, polyethylene, polypropylene, polyamide, etc. The method of covering the surface with the film is not particularly limited, and examples thereof include a method of attaching the film with an adhesive or the like, a method of wrapping the heat insulating material and the elastic sheet 51 with a film, and a method of storing the heat insulating material and the elastic sheet 51 in a bag-shaped film.

[0240] As shown in FIG. 21 and FIG. 22, in the case of a configuration in which the resin film contains the laminate, for example, a laminate including a heat insulating material 10 and an elastic sheet 51 is placed on a planar resin film, and the planar resin film is folded, for example, to cover the upper surface of the laminate with the planar resin film. Then, the planar film on the lower surface of the laminate and the planar resin film on the upper surface are heated while being pressed around the laminate to form a film fusion part 114. Then, the resin film around the laminate is shrunk by heating, and the resin film 112 is adhered to the outer surface of the laminate. Note that, at any timing before the resin film is shrunk, a plurality of holes 113 are formed in the resin film in the regions that will become the first surface side film 112a and the second surface side film 112b. By the above-mentioned process, a heat transfer-suppressing sheet can be manufactured.

[0241] In the second to fourth embodiments, the resin film 112, 312 and the covering material 323 have a plurality of elliptical holes, but these holes may be formed in an elliptical shape in advance, or may be formed into circular holes and then heat-shrunk the resin film to form an elliptical shape. When the resin film is heat-shrunk to form an elliptical shape, a method of adjusting the length of a pair of sides of the laminate and the length of a pair of fused parts in a direction parallel to the pair of sides, or the distance between the fused parts and the side of the folded flat resin film can be used. For example, when the length of a pair of fused parts in a direction parallel to the pair of sides of the laminate is brought close to the length of the pair of sides of the laminate, the force of the resin film to shrink is strengthened, and an elliptical hole having a major axis in a direction perpendicular to the pair of sides can be formed.

[0242] The method of enclosing the laminate in the resin film 112, 312 is not particularly limited, and includes shrink packaging in which the film is shrunk as described above, a method of wrapping the laminate in a resin film and then attaching it with an adhesive, a method of housing the laminate in a bag-shaped film, and the like. Regardless of the method used, as shown in Figures 21 and 22, the area ratio of the holes 113 in the first surface side film 112a and the second surface side film 112b can be made larger than the area ratio of the holes (not shown) in the end surface side film 112c. In Figures 21 and 22, it is preferable that the end surface side film 112c has a joint between the resin films.

[0243] Next, binder fibers and heating conditions that are preferably used in the method for producing the heat-transfer-suppressing sheet 50 according to this embodiment, as well as other binder materials, will be described.

[0244] <Binder fiber> In this embodiment, when using binder fibers 3 having a core-sheath structure, there is no particular limitation as long as the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath. The first organic material constituting the core may be at least one selected from polyethylene terephthalate, polypropylene, and nylon. The second organic material constituting the sheath may be at least one selected from polyethylene terephthalate, polyethylene, polypropylene, and nylon.

[0245] If the melting point of the first organic material constituting the core is sufficiently higher than that of the second organic material constituting the shell, the heating temperature setting margin in the heating step can be expanded, and the temperature setting for obtaining a desired structure can be made easier. For example, the melting point of the first organic material is preferably 60° C. or more higher than that of the second organic material, more preferably 70° C. or more higher, and even more preferably 80° C. or more higher.

[0246] Note that binder fibers 3 having the above-mentioned core-sheath structure are generally commercially available, and the materials constituting the core and sheath may be the same or different. Examples of binder fibers in which the core and sheath are made of the same material but have different melting points include those in which the core and sheath are made of polyethylene terephthalate, polypropylene, and nylon. Examples of binder fibers in which the core and sheath are made of different materials include those in which the core is made of polyethylene terephthalate and the sheath is made of polyethylene, and those in which the core is made of polypropylene and the sheath is made of polyethylene.

[0247] In this embodiment, the melting point of the second organic material constituting the sheath of the binder fiber 3 refers to the melting temperature at which the second organic material begins to melt and deform, but softening accompanied by a change in shape is also considered to be a type of melting deformation. The melting point of the sheath of the binder fiber can be measured, for example, by the following method. The binder fiber to be measured is placed in contact with the glass fiber having a higher melting point, heated from room temperature to, for example, 200°C at a heating rate of 5°C / min, and then cooled to room temperature. At this time, if the surface of the binder fiber melts and deforms and is fused at the part in contact with the glass fiber or the cross-sectional shape of the binder fiber changes, it can be determined that the melting point of the second organic material constituting the sheath is 200°C or less. In this embodiment, the heating temperature is changed in various ways, and the fusion state between the binder fiber and the glass fiber or the cross-sectional shape of the binder fiber after cooling is observed by the above-mentioned method, whereby the melting point of the second organic material constituting the sheath can be specified.

[0248] (Binder fiber content) In this embodiment, when binder fiber 3 having a core-sheath structure is used as the material, if the content of binder fiber in the mixture is appropriately controlled, the skeleton reinforcing effect of the resulting insulating material can be sufficiently obtained. The content of the binder fibers 3 is preferably 5% by mass or more, and more preferably 10% by mass or more, based on the total mass of the mixture. If the content of the binder fibers 3 is too high, the content of the inorganic particles 4 is relatively reduced, so in order to obtain the desired heat insulating performance, the content of the binder fibers 3 is preferably 25% by mass or less, and more preferably 20% by mass or less, based on the total mass of the mixture.

[0249] (Hot melt powder) In this embodiment, in addition to the binder fibers 3 and inorganic particles 4, the mixture may contain hot melt powder as a binder material. The hot melt powder is a powder that contains, for example, a third organic material different from the first organic material and the second organic material, and has the property of melting when heated. By adding the hot melt powder to the mixture and heating it, the hot melt powder melts, and when cooled, it hardens in a state including the surrounding inorganic particles 4. Therefore, it is possible to further suppress the falling off of the inorganic particles 4 from the heat insulating material.

[0250] There are various types of hot melt powders having various melting points, and a hot melt powder having an appropriate melting point can be selected in consideration of the melting points of the core and sheath of the binder fiber to be used. Specifically, if the third organic material, which is a component constituting the hot melt powder, has a melting point lower than that of the first organic material constituting the organic fiber, the heating temperature can be set to melt the sheath and hot melt powder while leaving the core. For example, if the melting point of the hot melt powder is lower than the melting point of the sheath, the heating temperature during production can be set between the melting points of the core and the sheath, making it even easier to set the heating temperature.

[0251] On the other hand, the type of hot melt powder used can be selected so that the melting point of the hot melt powder is between the melting points of the core and the sheath. When a hot melt powder having such a melting point is used, when the sheath and the hot melt powder are both melted and then cooled and hardened, the organic fiber (core) 1 and the molten sheath around it, and the hot melt powder present in the gaps between the inorganic particles 4 harden first. As a result, the position of the organic fiber 1 can be fixed, and then the molten sheath is welded to the organic fiber, making it easier to form a three-dimensional skeleton. Therefore, the strength of the entire sheet can be further improved.

[0252] If the melting point of the third organic material constituting the hot melt powder is sufficiently lower than that of the first organic material constituting the core, the heating temperature setting margin in the heating step can be expanded, and the temperature setting for obtaining a desired structure can be made easier. For example, the melting point of the first organic material is preferably 60° C. or more higher than the melting point of the third organic material, more preferably 70° C. or more higher, and even more preferably 80° C. or more higher.

[0253] The melting point of the hot melt powder (third organic material) is preferably 80° C. or higher, and more preferably 90° C. or higher. The melting point of the hot melt powder (third organic material) is preferably 180° C. or lower, and more preferably 150° C. or lower. Components constituting the hot melt powder include polyethylene, polyester, polyamide, ethylene vinyl acetate, and the like.

[0254] (Hot melt powder content) When hot melt powder is added to the mixture to suppress the falling off of inorganic particles, the effect of suppressing powder falling can be obtained even with a small amount of hot melt powder. Therefore, the content of hot melt powder is preferably 0.5% by mass or more, more preferably 1% by mass or more, based on the total mass of the mixture. On the other hand, when the content of the hot melt powder is increased, the content of the inorganic particles 4 and the like is relatively decreased, so in order to obtain the desired heat insulating performance, the content of the hot melt powder is preferably 5 mass % or less, and more preferably 4 mass % or less, relative to the total mass of the mixture.

[0255] <Heating conditions> When using binder fibers with a core-sheath structure as the material for the heat insulating material, the heating temperature in the heating step is preferably higher than the melting point of the second organic material constituting the sheath and lower than the melting point of the first organic material constituting the core. By setting the heating temperature in this manner, as described above, the strength of the sheet can be ensured by the core on both the surface side and the center side of the sheet, and the inorganic particles 4 can be held by the fused parts 5.

[0256] Specifically, the heating temperature in the heating step is set preferably 10° C. or more higher, more preferably 20° C. or more higher, than the melting point of the second organic material constituting the sheath, while the heating temperature is set preferably 10° C. or more lower, more preferably 20° C. or more lower, than the melting point of the first organic material constituting the core.

[0257] The heating time is not particularly limited, but it is preferable to set the heating time so that the sheath can be sufficiently melted, for example, from 3 minutes to 15 minutes.

[0258] When the heat insulating material contains hot melt powder, the heating temperature in the heating step is preferably set to be 10°C or more higher than the higher of the melting point of the second organic material constituting the sheath and the melting point of the third organic material constituting the hot melt powder, and more preferably set to be 20°C or more higher. On the other hand, the heating temperature is preferably set to be 10°C or more lower than the melting point of the first organic material constituting the core, and more preferably set to be 20°C or more lower. By setting the heating temperature at such a level, a strong skeleton can be formed, the strength of the sheet can be further improved, and the inorganic particles 4 can be prevented from falling off by the fused parts 5, etc.

[0259] <Thickness of heat transfer suppression sheet> The thickness of the heat-transfer-suppressing sheet according to the present embodiment is not particularly limited, but is preferably 0.05 mm or more and 10 mm or less. If the thickness is 0.05 mm or more, sufficient compressive strength can be obtained. On the other hand, if the thickness is 10 mm or less, the heat-transfer-suppressing sheet can have good thermal insulation properties.

[0260] [Battery pack] An example of a battery pack to which the heat-transfer-suppressing sheet 50 according to the embodiment of the present invention is applied is as shown in FIG. 2. The configuration and effects of the battery pack will now be specifically described with reference to FIG. 2. As described above, the heat-transfer-suppressing sheet 50 shown in FIG. 2 can be replaced with the heat-transfer-suppressing sheets 120, 130, 140, 150, 160, 170, 180, 190 having other structures, as well as with heat-transfer-suppressing sheets having other structures within the scope of the present invention. Furthermore, the heat insulating material 10 can be replaced with other heat insulating materials within the scope of the present invention, as well as with the heat insulating materials having the various structures described above.

[0261] 2, the battery pack 100 includes a plurality of battery cells 20a, 20b, and 20c, and a heat-transfer-reducing sheet 50 according to the present embodiment, with the plurality of battery cells being connected in series or in parallel. For example, the heat-transfer-reducing sheet 50 according to the present embodiment is interposed between the battery cells 20a and 20b, and between the battery cells 20b and 20c. Furthermore, the battery cells 20a, 20b, and 20c and the heat-transfer-reducing sheet 50 are housed in a battery case 30. The heat-transfer-suppressing sheet 50 is as described above.

[0262] In the battery pack 100 configured in this manner, since the heat-transfer-suppressing sheet has high thermal insulation properties, even if a certain battery cell 20a becomes hot, the heat transfer to the battery cell 20b can be suppressed because the heat-transfer-suppressing sheet 50, which has a heat-transfer-suppressing effect, is present between the battery cell 20a and the battery cell 20b. Furthermore, since the heat-transfer-suppressing sheet in the battery pack according to this embodiment has an elastic sheet, it is possible to suppress the application of unnecessary pressure to the battery cell during charging / discharging or when an abnormality occurs. As a result, it is possible to suppress the deterioration of battery performance and improve durability.

[0263] The battery pack 100 of this embodiment is not limited to the battery pack illustrated in Fig. 2. For example, the heat transfer-suppressing sheet 50 may be disposed not only between the battery cells 20a and 20b and between the battery cells 20b and 20c, but also between the battery cells 20a, 20b, and 20c and the battery case 30, or may be attached to the inner surface of the battery case 30.

[0264] In the battery pack 100 configured in this manner, if a battery cell catches fire, it is possible to prevent the flame from spreading outside the battery case 30. For example, the battery pack 100 according to this embodiment may be used in an electric vehicle (EV) or the like, and may be placed under the floor of a passenger compartment. In this case, even if a battery cell catches fire, the safety of the passengers can be ensured. Furthermore, since the heat transfer suppression sheet 50 can be disposed not only between each battery cell but also between the battery cells 20a, 20b, 20c and the battery case 30, there is no need to fabricate new flame retardant materials, etc., and a safe battery pack 100 can be easily constructed at low cost.

[0265] In the battery pack of this embodiment, the heat-transfer-suppressing sheet 50 arranged between the battery cells 20a, 20b, 20c and the battery case 30 may be in contact with the battery cells or may have a gap between them. The heat-transfer-suppressing sheet of this embodiment has an elastic sheet, and therefore can allow deformation of the battery cells even if the temperature of any of the multiple battery cells rises and the volume expands.

[0266] The heat-transfer-suppressing sheet according to this embodiment can be manufactured into various shapes depending on the manufacturing method. Therefore, it can be adapted to any shape without being affected by the shapes of the battery cells 20a, 20b, 20c and the battery case 30. Specifically, it can be applied to cylindrical batteries, flat batteries, etc. in addition to square batteries. [Explanation of symbols]

[0267] 1. Organic Fibers 3. Binder Fiber 4 Inorganic particles 5 Welded area 6,47 Fiber bundle 7 Vacancies 8 Cavity 10,40,60,70,80,90,110 Insulation 11 Fiber layer 15 Inorganic fibers 16 Textile Department 20a, 20b, 20c Battery cells 28 Air Layer 30 Battery case 32 Base 33 branches 50,120,130,140,150,160,170,180,190 Heat transfer suppression sheet 51,751 Elastic sheet 100 battery packs 111,311,511 Laminate 112,312 Resin film 113 holes 114 Film fusion section 313,323 Covering materials 316 Fusion part 317 Gap 512,514 Bulge control sheet

Claims

1. A heat insulating material having inorganic particles and organic or inorganic fibers; a heat transfer suppression sheet having an elastic sheet laminated on at least one of a first surface and a second surface of the heat insulating material which are perpendicular to the thickness direction of the heat insulating material.

2. The heat transfer suppressing sheet according to claim 1 , wherein the heat insulating material has a plurality of pores that are three-dimensionally connected.

3. 2. The heat transfer suppression sheet according to claim 1, characterized in that, when the insulating material contains organic fibers, the organic fibers have a welded portion covering at least a portion of a surface thereof, and at least a portion of the inorganic particles are welded to the organic fibers by the welded portion.

4. In the thermal insulation material, the organic fiber is made of a first organic material, and the welded portion includes a second organic material; The heat transfer suppressing sheet according to claim 3 , wherein the melting point of the second organic material is lower than the melting point of the first organic material.

5. 5. The heat-transfer-suppressing sheet according to claim 4, wherein in the heat insulating material, the melting point of the second organic material is lower than the melting point of the first organic material by 60[deg.] C. or more.

6. In the thermal insulation material, the first organic material is at least one selected from polyethylene terephthalate, polypropylene, and nylon, 5. The heat transfer suppressing sheet according to claim 4, wherein the second organic material is at least one selected from the group consisting of polyethylene terephthalate, polyethylene, polypropylene, and nylon.

7. The heat transfer-suppressing sheet according to claim 1 , wherein the heat insulating material essentially contains the inorganic fibers.

8. 8. The heat transfer-suppressing sheet according to claim 7, wherein the inorganic fibers are at least one selected from the group consisting of silica-alumina fibers, alumina fibers, silica fibers, rock wool, alkaline earth silicate fibers, and glass fibers.

9. The heat transfer suppressing sheet according to claim 3 , characterized in that the heat insulating material has a fiber layer on at least a portion of the first surface and the second surface, in which at least a portion of a plurality of the organic fibers are welded to each other by the welding portion.

10. The heat insulating material further comprises inorganic fibers, The heat transfer suppressing sheet according to claim 9 , wherein the fiber layer contains the inorganic fiber.

11. 2. The heat transfer-suppressing sheet according to claim 1, wherein in the heat insulating material, the inorganic particles are particles made of at least one type of inorganic material selected from the group consisting of oxide particles, carbide particles, nitride particles, and inorganic hydrate particles.

12. 10. The heat transfer suppressing sheet according to claim 9, wherein in the heat insulating material, the inorganic particles include at least one type of particles selected from dry silica particles and silica aerogel.

13. 13. The heat transfer suppressing sheet according to claim 12, wherein in the heat insulating material, the inorganic particles further include at least one type of particles selected from the group consisting of titania, zircon, zirconia, silicon carbide, zinc oxide, and alumina.

14. The insulating material and the elastic sheet are further provided with a resin film that encloses a laminate having the insulating material and the elastic sheet, the resin film has a plurality of holes, and is composed of a first surface side film and a second surface side film arranged on the first surface side and the second surface side of the laminate perpendicular to the thickness direction of the laminate, and an end surface side film arranged on an end surface side parallel to the thickness direction of the laminate, A heat transfer suppressing sheet as described in any one of claims 1 to 13, characterized in that the area ratio of the holes in the first surface side film and the second surface side film to the total area of ​​the first surface side film and the second surface side film is greater than the area ratio of the holes in the end surface side film to the total area of ​​the end surface side film.

15. 14. A battery pack comprising a plurality of battery cells and the heat transfer-suppressing sheet according to claim 1, the plurality of battery cells being connected in series or in parallel.

16. An assembled battery comprising: a plurality of battery cells; and the heat transfer-suppressing sheet according to claim 14, the plurality of battery cells being connected in series or in parallel.

Citation Information

Patent Citations

  • Battery pack

    JP2004146161A

  • Battery pack

    JP2014096271A

Cited By

  • Fire prevention sheet for use between battery cells and method for manufacturing the fire prevention sheet

    JP7840092B1

  • Concentration monitoring system, concentration management system, and concentration monitoring method

    US12360127B2

  • Elastic sheet and method for producing same, heat transfer suppression sheet, and battery pack

    WO2026172673A1